Lead-acid battery
Patent Information
- Application Number
- JP2020197593
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-11-27
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2040-11-27
AI Technical Summary
【0013】 高いHR放電性能を確保しながら、優れた高温フロート寿命性能が得られる鉛蓄電池を提供できる。
Smart Images

Figure 0007643016000006 
Figure 0007643016000007 
Figure 0007643016000008
Abstract
Description
[Technical field]
[0001] The present invention relates to a lead-acid battery. [Background technology]
[0002] Lead-acid batteries are used in a variety of applications, including automotive and industrial use. Lead-acid batteries include a negative electrode plate, a positive electrode plate, a separator (or mat), and an electrolyte. Each electrode plate includes a current collector and an electrode material.
[0003] In order to impart various functions, additives are sometimes added to the components of lead-acid batteries.
[0004] For example, Patent Document 1 proposes a lead-acid battery characterized in that the electrolyte and / or the electrode active material molded body contain a polymer compound containing any one selected from the group consisting of polyvinyl alcohol, polyethylene glycol, polyvinylpyrrolidone, polyacrylic acid, and esters thereof, each having a degree of polymerization of 30 to 3,000, or the polymer compound and colloidal barium sulfate particles.
[0005] Patent Document 2 proposes a negative electrode plate for a lead-acid battery in which a paste-type active material containing a shrinkage inhibitor is filled into a current collector, the negative electrode plate being characterized in that polyoxyperfluoroethylenephenylamine represented by a specific chemical formula is used as the shrinkage inhibitor, and the content of the polyoxyperfluoroethylenephenylamine is 0.005 to 3% by weight of the paste-type active material.
[0006] It has also been proposed to adjust the surface area of the negative plate.
[0007] For example, Patent Document 3 discloses a sealed lead-acid battery that is made up of a positive electrode plate, a negative electrode plate, a separator that also serves as an electrolyte impregnating material, a dilute sulfuric acid electrolyte, and a synthetic resin battery case, and in which the amount of electrolyte is limited to such an extent that there is almost no free electrolyte, and in which the surface area of the negative plate per 20-hour rate discharge capacity is set to 24 to 30 cm 2 / Ah.
[0008] Patent Document 4 specifies the surface area of the negative electrode plate constituting the cell as 45 cm per 3-hour rate discharge capacity in a 25°C atmosphere. 2 / Ah or more 85cm 2 / Ah or less. [Prior art documents] [Patent documents]
[0009] [Patent Document 1] JP 2000-149981 A [Patent Document 2] Japanese Patent Application Publication No. 9-147874 [Patent Document 3] Japanese Patent Application Publication No. 11-191409 [Patent Document 4] JP 2009-140739 A Summary of the Invention [Problem to be solved by the invention]
[0010] In recent years, there has been an increasing demand for lead-acid batteries with high high-rate (HR) discharge performance. Increasing the opposing area of the positive and negative plates reduces the internal resistance and improves HR discharge performance. On the other hand, the thickness of each plate is reduced, and the problem of corrosion of the positive electrode current collector becomes apparent when float charging is performed at high temperatures. As a result, the life performance when charging and discharging, including float charging, is performed at high temperatures (hereinafter, sometimes referred to as high-temperature float life performance) is quickly reduced. There is a trade-off between HR discharge performance and high-temperature float life performance, and it is difficult to achieve both at the same time. [Means for solving the problem]
[0011] A first aspect of the present invention is a lead-acid battery, The lead-acid battery includes at least one cell including a plate group and an electrolyte; the electrode plate group includes a negative electrode plate, a positive electrode plate, and a separator interposed between the negative electrode plate and the positive electrode plate, The negative electrode plate includes a negative electrode current collector and a negative electrode material, The positive electrode plate includes a positive electrode current collector and a positive electrode material, The negative electrode material is measured using deuterated chloroform as a solvent. 1 The polymer compound has a peak in the range of 3.2 ppm to 3.8 ppm in the chemical shift of H-NMR spectrum, The Ca content in the positive electrode current collector is 0.07% by mass or less, The opposing area of the positive electrode plate and the negative electrode plate per 1 Ah of 10-hour capacity is 2450 mm 2 / Ah or more 6700mm 2 / Ah or less.
[0012] A second aspect of the present invention is a lead-acid battery, The lead-acid battery includes at least one cell including a plate group and an electrolyte; the electrode plate group includes a negative electrode plate, a positive electrode plate, and a separator interposed between the negative electrode plate and the positive electrode plate, The negative electrode plate includes a negative electrode current collector and a negative electrode material, The positive electrode plate includes a positive electrode current collector and a positive electrode material, The negative electrode material is oxyC 2-4 The polymer compound includes a repeating structure of an alkylene unit, The Ca content in the positive electrode current collector is 0.07% by mass or less, The opposing area of the positive electrode plate and the negative electrode plate per 1 Ah of 10-hour capacity is 2450 mm 2 / Ah or more 6700mm 2 / Ah or less. Effect of the Invention
[0013] This makes it possible to provide a lead-acid battery that can achieve excellent high-temperature float life performance while ensuring high HR discharge performance. [Brief description of the drawings]
[0014] [Figure 1] FIG. 1 is a perspective view showing a lead-acid battery according to one aspect of the present invention with a lid removed. [Figure 2A] FIG. 2 is a front view of the lead-acid battery of FIG. [Figure 2B] 2B is a schematic cross-sectional view of the lead-acid battery taken along line IIB-IIB in FIG. 2A, viewed from the direction of the arrows. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] As the use of lead-acid batteries expands, the demand for lead-acid batteries with high HR discharge performance is increasing. For example, in many industrial stationary batteries for uninterruptible power supplies (UPS), HR discharge was previously assumed to be at a 10-hour rate. However, in recent years, there has been an increasing demand for high HR discharge performance under harsh conditions such as a 15-minute rate or 5-minute rate.
[0016] For example, by increasing the area of the positive plate facing the negative plate, the internal resistance can be reduced, and the HR discharge performance can be improved. By increasing the number of positive and negative plates, the facing area can be easily increased. However, as the number of plates increases, the thickness of the plates decreases, and the problem of corrosion of the positive electrode collector is likely to become apparent. The corrosion of the positive electrode collector is particularly noticeable during float charging at high temperatures. Therefore, the life performance (high-temperature float life performance) when discharging at HR after float charging at high temperatures is reduced. Therefore, it is difficult to obtain excellent high-temperature float life performance while maintaining high HR discharge performance.
[0017] In view of the above, a lead-acid battery according to a first aspect of the present invention includes at least one cell including an electrode plate group and an electrolyte. The electrode plate group includes a negative electrode plate, a positive electrode plate, and a separator interposed between the negative electrode plate and the positive electrode plate. The negative electrode plate includes a negative electrode current collector and a negative electrode material. The positive electrode plate includes a positive electrode current collector and a positive electrode material. The negative electrode material is measured using deuterated chloroform as a solvent. 1The polymer compound has a peak in the range of 3.2 ppm to 3.8 ppm in the chemical shift of the H-NMR spectrum. The Ca content in the positive electrode current collector is 0.07 mass % or less. The facing area of the positive electrode plate and the negative electrode plate per 1 Ah of 10-hour rate capacity is 2450 mm 2 / Ah or more 6700mm 2 / Ah or less. In addition, 1 In the H-NMR spectrum, the peaks appearing in the chemical shift range of 3.2 ppm to 3.8 ppm are oxy-C 2-4 It comes from an alkylene unit.
[0018] A lead-acid battery according to a second aspect of the present invention includes at least one cell including an electrode plate group and an electrolyte. The electrode plate group includes a negative electrode plate, a positive electrode plate, and a separator interposed between the negative electrode plate and the positive electrode plate. The negative electrode plate includes a negative electrode current collector and a negative electrode material. The positive electrode plate includes a positive electrode current collector and a positive electrode material. The negative electrode material is oxyC. 2-4 The positive electrode current collector contains a polymer compound having a repeating structure of alkylene units. The Ca content in the positive electrode current collector is 0.07 mass% or less. The facing area of the positive electrode plate and the negative electrode plate per 10-hour rate capacity of 1 Ah is 2450 mm 2 / Ah or more 6700mm 2 / Ah or less.
[0019] Hereinafter, the facing area of the positive electrode plate with the negative electrode plate per 1 Ah of 10-hour rate capacity may be simply referred to as the "facing area" of the positive electrode plate with the negative electrode plate.
[0020] In the lead-acid battery according to each of the first and second aspects, a negative electrode plate including a negative electrode material containing the above-mentioned polymer compound is combined with a positive electrode plate including a positive electrode current collector having a Ca content of 0.07% by mass or less, and the facing area of the positive electrode plate with respect to the negative electrode plate is set to 2450 mm 2 / Ah or more 6700mm 2 / Ah or less. With this configuration, it is possible to obtain excellent high temperature float life performance while ensuring high HR discharge performance in the lead acid battery.
[0021] In the lead-acid batteries according to the first and second aspects, the reason why excellent high-temperature float life performance can be ensured while high HR discharge performance is ensured is believed to be as follows.
[0022] First, the area of the positive plate facing the negative plate is 2450 mm 2 / Ah or more, high HR discharge performance can be obtained. For example, even under severe HR conditions such as 15% or 5% HR, the discharge reaction can proceed smoothly. When the area of the positive electrode plate facing the negative electrode plate becomes large, the thickness of the plate becomes small, so that corrosion of the positive electrode collector tends to become more noticeable during float charging at high temperatures (for example, about 60°C). However, by controlling the Ca content in the positive electrode collector to 0.07 mass% or less, the corrosion of the positive electrode collector can be reduced to some extent. The corrosion resistance of the positive electrode collector tends to improve as the Ca content in the positive electrode collector is reduced.
[0023] The polymer compound contained in the negative electrode material is oxyC 2-4 Since the repeating structure of the alkylene unit makes it easy to form a linear structure, the surface of the lead in the negative electrode material is thinly and widely covered with the polymer compound. When the surface of the lead is covered with the polymer compound in a wide area of the lead surface, the hydrogen overvoltage in the negative plate increases, and the potential of the negative plate shifts in a more base direction. Accordingly, the potential of the positive plate also shifts in a more base direction, and the rate of corrosion of the positive electrode collector slows down. By using the polymer compound as the negative electrode material in a state in which the corrosion of the positive electrode collector is reduced by controlling the Ca content, the effect of shifting the potential of each electrode plate by the polymer compound is more effectively exerted, and the corrosion of the positive electrode collector can be significantly suppressed. This allows for high high-temperature float life performance to be obtained. In other words, even if the thickness of the positive electrode collector is made small enough to ensure high HR discharge performance, the corrosion of the positive electrode collector during high-temperature float charging can be reduced, and the life performance can be improved. The effect of such a polymer compound is observed when the facing area of the positive plate and the negative plate is 6700 mm 2 / Ah or less. Also, when the Ca content exceeds 0.07 mass% or the facing area is 6700 mm 2 When the capacity exceeds 1000mA / Ah, the effect of corrosion of the positive electrode current collector becomes very large among the effects on the life performance, and even if a polymer compound is used as a negative electrode material, the improvement in life performance is hardly obtained, or even if it is obtained, it is very small.
[0024] In addition, when an organic additive is contained in the negative electrode material, if the organic additive becomes unevenly distributed in the pores of the lead, the movement of ions (lead ions, sulfate ions, etc.) in the pores of the negative electrode material is hindered, and the HR discharge performance is reduced. However, the thickness of the coating of the above-mentioned polymer compound covering the surface of the lead in the negative electrode material is thin, and the uneven distribution of the polymer compound is suppressed. Since the steric hindrance caused by the polymer compound coating is small, the hindrance of the movement of ions in the pores of the negative electrode material is reduced. Therefore, the high HR discharge performance obtained by controlling the opposing area of each electrode plate can be maintained.
[0025] The effect of improving the high-temperature float life performance is exhibited by covering the surface of lead with a polymer compound, and can be obtained even with a very small amount of the polymer compound contained in the negative electrode material. Therefore, by including a polymer compound in the negative electrode material, it is possible to make it exist in the vicinity of the lead, and this allows the oxy C 2-4 It is believed that the alkylene unit exerts a high adsorption effect on lead. Since it is important that the polymer compound is present in the vicinity of lead, it is important that the negative electrode material contains a polymer compound, regardless of whether or not the components of the lead-acid battery other than the negative electrode material contain a polymer compound.
[0026] In addition, when discharging at a low rate after float charging at high temperature, the opposing area of the positive plate and the negative plate is 2450 mm 2 / Ah or more and 2450mm 2There is almost no difference in life performance when the discharge rate is less than 1000 / Ah, and excellent life performance is obtained in either case. In other words, the behavior of the life period when the facing area of the positive plate and the negative plate is changed is completely different when the discharge rate after high-temperature float charging is high or low. In the case of low-rate discharge conditions, the problem of the life period after the high-temperature float test being reduced due to the difference in the facing area of the positive plate and the negative plate does not occur.
[0027] The area of the positive and negative plates facing each other is 6500 mm 2 / Ah or less. In this case, the effect of the polymer compound is more easily exhibited, and corrosion of the positive electrode current collector during high-temperature float charging is further reduced, resulting in a higher high-temperature float life performance.
[0028] When the positive electrode current collector contains Ca, in order to improve the corrosion resistance of the positive electrode current collector, the positive electrode current collector or the lead alloy constituting the positive electrode current collector may further contain Sn, for example, may be composed of a Pb-Ca-Sn alloy. The positive electrode current collector may contain Sn, but when the Ca content is 0.07 mass% or less, the Sn content is preferably 7 mass% or less. The Ca content in the positive electrode current collector may be 0.01 mass% or more. In these cases, the balance between the Ca content and the Sn content further reduces the corrosion of the positive electrode current collector during high-temperature float charging, and a higher life performance is obtained.
[0029] The Sn content in the positive electrode current collector may be 0.01% by mass or more. In this case, Sn is easily precipitated at the grain boundaries of metal crystal grains in the positive electrode current collector, and corrosion originating from the grain boundaries (so-called intergranular corrosion) is less likely to progress, so that the effect of improving the high-temperature float life performance is considered to be remarkable. In particular, when the positive electrode current collector contains Ca, by setting the Sn content in this range, a higher life performance can be ensured.
[0030] When the Ca content in the positive electrode current collector is less than 0.01% by mass, the Sn content is preferably 1.5% by mass or less. When a polymer compound is used as the negative electrode material and the Ca content of the positive electrode current collector is less than 0.01% by mass, the high-temperature float battery life is further significantly improved. When the Ca content of the positive electrode current collector is less than 0.01% by mass, even if the Sn content is as low as 1.5% by mass or less, grain boundary corrosion is less likely to progress, so that the effect of improving the battery life is considered to be remarkable.
[0031] In a lead acid battery according to one aspect of the present invention, the polymer compound may include oxygen atoms bonded to end groups and -CH2- and / or -CH< groups bonded to the oxygen atoms. 1 In the H-NMR spectrum, the ratio of the integral value of the peak between 3.2 ppm and 3.8 ppm to the total integral value of this peak, the integral value of the peak of the hydrogen atom of the -CH2- group bonded to the oxygen atom, and the integral value of the peak of the hydrogen atom of the -CH< group bonded to the oxygen atom is preferably 85% or more. 2-4 The molecule contains many alkylene units. Therefore, the polymer compound is more easily adsorbed to lead and more easily forms a linear structure, which makes it easier to thinly cover the lead surface. This is thought to suppress uneven distribution of the polymer compound and enhance the effect of shifting the potential of the plate in a more base direction. Therefore, it is possible to ensure higher high-temperature float life performance while maintaining the high HR discharge performance of the lead-acid battery.
[0032] 1 Polymer compounds that have a peak in the chemical shift range of 3.2 ppm to 3.8 ppm in the H-NMR spectrum are oxyC 2-4 It is preferable that the alkylene unit contains a repeating structure. 2-4When a polymer compound containing a repeating structure of alkylene units is used, the polymer compound is more easily adsorbed to lead, and since the polymer compound is more likely to have a linear structure, it is easier to thinly cover the lead surface, which is thought to suppress uneven distribution. Therefore, it is possible to ensure higher high-temperature float life performance while maintaining the high HR discharge performance of the lead-acid battery.
[0033] The polymer compound is OxyC 2-4 The hydroxy compound may include at least one selected from the group consisting of a hydroxy compound having a repeating structure of an alkylene unit, an etherified product of a hydroxy compound, and an esterified product of a hydroxy compound. 2-4 Alkylene glycol, oxy C 2-4 Copolymers containing repeating alkylene units, and polyol polyC 2-4 At least one selected from the group consisting of alkylene oxide adducts. When such a polymer compound is used, it is believed that the lead surface is easily covered thinly and widely, and uneven distribution is suppressed. Therefore, it is possible to ensure higher high-temperature float life performance while maintaining high HR discharge performance.
[0034] The polymer compound may contain a repeating structure of an oxypropylene unit (-O-CH(-CH3)-CH2-). Such a polymer compound is considered to have an excellent balance between high adsorption to lead and suppressed thick adhesion to the lead surface. Furthermore, when the polymer compound contains a repeating structure of an oxypropylene unit, the charge acceptance tends to be lower than when the polymer compound contains a repeating structure of an oxyethylene unit. However, the lead-acid batteries according to the first and second aspects of the present invention can ensure higher high-temperature float life performance while maintaining high HR discharge performance.
[0035] The polymer compound has one or more hydrophobic groups, and at least one of the hydrophobic groups may be a long-chain aliphatic hydrocarbon group having 8 or more carbon atoms. The action of such a hydrophobic group suppresses excessive coating of the polymer compound on the lead surface, and the uneven distribution of the polymer compound can be more effectively suppressed. It is also preferable that the polymer compound contains a repeating structure of an oxyethylene unit. By containing a repeating structure of an oxyethylene unit having high hydrophilicity, it can be selectively adsorbed to lead. Therefore, by the balance between the hydrophobic group and the hydrophilic group, it is possible to ensure higher high-temperature float life performance while maintaining the high HR discharge performance of the lead-acid battery.
[0036] Thus, since the polymer compound has high adsorption to lead, but can thinly cover the lead surface, even if the content of the polymer compound in the negative electrode material is small, the effect of shifting the potential of the negative electrode plate in the less noble direction is obtained, and therefore high charge acceptance in the negative electrode plate is easily ensured. In addition, the potential of the positive electrode plate is also shifted in the less noble direction, and the corrosion of the positive electrode current collector during high-temperature float charging can be reduced, so that high life performance can be obtained. From the viewpoint of easily obtaining higher high-temperature float life performance by further enhancing the effect of suppressing the decrease in charge acceptance, the content of the polymer compound in the negative electrode material is preferably 5000 ppm or less by mass. From the viewpoint of obtaining higher high-temperature float life performance by further enhancing the effect of shifting the potential of the positive electrode plate in the less noble direction, the content of the polymer compound in the negative electrode material is preferably 3 ppm or more.
[0037] In the lead-acid battery, the origin of the polymer compound contained in the negative electrode material is not particularly limited as long as the polymer compound can be contained in the negative electrode material. When the lead-acid battery is produced, the polymer compound may be contained in any of the components of the lead-acid battery (e.g., the negative electrode plate, the positive electrode plate, the electrolyte, and the separator). The polymer compound may be contained in one component, or in two or more components (e.g., the negative electrode plate and the electrolyte).
[0038] The ratio of the theoretical amount of electricity of the negative electrode material to the theoretical amount of electricity of the positive electrode material (=theoretical amount of electricity of the negative electrode material / theoretical amount of electricity of the positive electrode) is preferably 0.7 to 1.3. In this case, it is easy to balance the utilization rate of the active material between the positive and negative electrode plates, and a higher discharge capacity can be secured at an early stage, so that a higher high-temperature float life performance can be secured.
[0039] The lead acid battery may be either a valve regulated (sealed) lead acid battery (VRLA type lead acid battery) or a flooded (vented) lead acid battery. The first and second aspects of the present invention are particularly suitable for valve regulated lead acid batteries.
[0040] In this specification, the content of the polymer compound in the negative electrode material, the Ca content and the Sn content in the positive electrode current collector, the opposing area of the positive electrode plate with the negative electrode plate, and the theoretical electrical capacity of each electrode plate are determined for a negative electrode plate or a positive electrode plate taken out of a fully charged lead-acid battery.
[0041] (Terminology explanation) (electrode material) The negative electrode material and the positive electrode material are usually held by a current collector. The electrode material is the portion of the electrode plate excluding the current collector. A member such as a mat or pasting paper may be attached to the electrode plate. Such a member (also called an attachment member) is included in the electrode plate because it is used integrally with the electrode plate. When the electrode plate includes an attachment member (such as a mat or pasting paper), the electrode material is the portion of the electrode plate excluding the current collector and the attachment member.
[0042] Among the positive plate, the clad type positive plate includes a plurality of porous tubes, a metal core inserted into each tube, a current collector connecting the plurality of metal cores, a positive electrode material filled in the tube into which the metal core is inserted, and a connecting seat connecting the plurality of tubes. In the clad type positive plate, the positive electrode material is the portion of the plate excluding the tube, the metal core, the current collector, and the connecting seat. In the clad type positive plate, the metal core and the current collector are sometimes collectively referred to as the positive electrode current collector.
[0043] (Polymer Compound) The polymer compound satisfies at least one of the following conditions (i) and (ii). Condition (i) Polymer compounds are measured using deuterated chloroform as a solvent. 1 In the H-NMR spectrum, it has a peak in the range of 3.2 ppm to 3.8 ppm. Condition (ii) The polymer compound is OxyC 2-4 It contains a repeating structure of alkylene units.
[0044] Under condition (i), the peak in the range of 3.2 ppm to 3.8 ppm is oxy-C 2-4 The polymer compound is derived from an alkylene unit. In other words, the polymer compound satisfying the condition (ii) is also a polymer compound satisfying the condition (i). The polymer compound satisfying the condition (i) is an oxyC 2-4 The polymer compound may contain a repeating structure of a monomer unit other than an alkylene unit, and may have a certain molecular weight. The number average molecular weight (Mn) of the polymer compound satisfying the above (i) or (ii) may be, for example, 300 or more.
[0045] (Oxy C 2-4 Alkylene unit) Oxy C 2-4 The alkylene unit is -OR 1 -(R 1 is C 2-4 It is a unit represented by the formula:
[0046] (number average molecular weight) In the present specification, the number average molecular weight (Mn) is determined by gel permeation chromatography (GPC). The standard substance used in determining Mn is polyethylene glycol.
[0047] (Area of the positive electrode facing the negative electrode) The facing area of the positive plate with the negative plate per 1 Ah of 10-hour rate capacity is the area (mm 2 ) and dividing it by the 10-hour rate capacity (Ah) of the lead-acid battery. The area of the positive plate facing the negative plate is the area of the overlapping portion of the projection shapes of the part of the positive plate where the positive electrode material exists and the part of the negative plate where the negative electrode material exists, projected in the thickness direction of the plate. The area of the positive plate facing the negative plate is the same as the area of the part of the negative plate facing the positive plate.
[0048] (Theoretical Electrical Ratio) The ratio of the theoretical amount of electricity of the negative plate to the theoretical amount of electricity of the positive plate (hereinafter sometimes referred to as the theoretical amount of electricity ratio) is calculated by dividing the theoretical amount of electricity of the negative plate by the theoretical amount of electricity of the positive plate. The theoretical amount of electricity of the negative plate is calculated by multiplying the mass (g) of lead contained in the negative electrode material of all negative plates included in the lead-acid battery by the electrical capacity of 0.2587 Ah per gram of Pb atom. The theoretical amount of electricity of the positive plate is calculated by multiplying the mass (g) of lead contained in the positive electrode material of all positive plates included in the lead-acid battery by 0.2587 Ah.
[0049] (fully charged) The fully charged state of a flooded lead-acid battery is defined by JIS D 5301:2019. More specifically, the fully charged state is defined as a state in which the lead-acid battery is charged in a water tank at 25°C ± 2°C with a current (A) 0.2 times the value (unit: Ah) listed as the rated capacity until the terminal voltage (V) during charging or the electrolyte density converted to a temperature of 20°C shows a constant value with three significant digits three consecutive times. In addition, in the case of a valve-regulated lead-acid battery, the fully charged state is defined as a state in which constant-current constant-voltage charging of 2.23 V / cell is performed in an air tank at 25°C ± 2°C with a current (A) 0.2 times the value (unit: Ah) listed as the rated capacity, and charging is terminated when the charging current during constant-voltage charging becomes 0.005 times the value (unit: Ah) listed as the rated capacity.
[0050] A fully charged lead-acid battery refers to a lead-acid battery that has already been chemically prepared and is fully charged. A lead-acid battery may be fully charged immediately after chemical preparation, or after a certain amount of time has passed since chemical preparation (for example, a lead-acid battery that is in use (preferably in the early stages of use) after chemical preparation may be fully charged). An early stage battery refers to a battery that has not been in use for very long and has hardly deteriorated at all.
[0051] (Top and bottom directions of lead-acid batteries or components of lead-acid batteries) In this specification, the up-down direction of a lead-acid battery or components of the lead-acid battery (such as plates, a battery case, and a separator) refers to the up-down direction in the vertical direction of the lead-acid battery when the lead-acid battery is in use. Each of the positive and negative plates has a lug for connecting to an external terminal. In some cases, such as a horizontal valve-regulated lead-acid battery, the lug is provided on the side of the plate so as to protrude laterally, but in most lead-acid batteries, the lug is usually provided on the top of the plate so as to protrude upward.
[0052] Hereinafter, the lead-acid battery according to the embodiment of the present invention will be described in detail with respect to each of its main components, but the present invention is not limited to the following embodiment.
[0053] [Lead acid battery] (Negative plate) The negative electrode plate usually includes a negative electrode current collector in addition to a negative electrode material.
[0054] (Negative electrode current collector) The negative electrode current collector may be formed by casting lead (Pb) or a lead alloy, or may be formed by processing a lead sheet or a lead alloy sheet. Examples of the processing method include expanding and punching. It is preferable to use a lattice-shaped current collector as the negative electrode current collector because it is easy to support the negative electrode material.
[0055] The lead alloy used for the negative electrode current collector may be any of Pb-Sb alloy, Pb-Ca alloy, and Pb-Ca-Sn alloy. These lead or lead alloys may further contain at least one selected from the group consisting of Ba, Ag, Al, Bi, As, Se, Cu, etc. as an additive element. The negative electrode current collector may have a surface layer. The surface layer and the inner layer of the negative electrode current collector may have different compositions. The surface layer may be formed on a part of the negative electrode current collector. The surface layer may be formed on the ear of the negative electrode current collector. The surface layer of the ear may contain Sn or an Sn alloy.
[0056] (Negative electrode material) The negative electrode material includes the above polymer compound. The negative electrode material further includes a negative electrode active material (specifically, lead or lead sulfate) that develops capacity through an oxidation-reduction reaction. The negative electrode material may include at least one selected from the group consisting of an organic shrinkage inhibitor, a carbonaceous material, and other additives. Examples of additives include barium sulfate and fibers (such as resin fibers). However, the additives are not limited to these. The negative electrode active material in a charged state is sponge-like lead, but an unformed negative plate is usually made using lead powder.
[0057] (Polymer Compound) The polymer compound is 1 In the chemical shift of the H-NMR spectrum, the peak is in the range of 3.2 ppm to 3.8 ppm. Such a polymer compound is an oxyC 2-4 Contains alkylene units. OxyC 2-4 Examples of the alkylene unit include an oxyethylene unit, an oxypropylene unit, an oxytrimethylene unit, an oxy2-methyl-1,3-propylene unit, an oxy1,4-butylene unit, and an oxy1,3-butylene unit. 2-4 The alkylene unit may have one type or two or more types.
[0058] The polymer compound is OxyC 2-4It is preferred that the repeating structure of the alkylene unit is a type of oxy C 2-4 may contain an alkylene unit, 2-4 The polymer compound may contain one type of the repeating structure or two or more types of the repeating structures.
[0059] Oxy C 2-4 Polymer compounds having a repeating structure of alkylene units also include polymer compounds classified as surfactants (more specifically, nonionic surfactants).
[0060] Examples of the polymer compound include oxy C 2-4 Poly(C) is a hydroxy compound with repeating alkylene units. 2-4 Alkylene glycol, oxy C 2-4 Polyol polyC, a copolymer containing repeating alkylene units 2-4 alkylene oxide adducts, and ethers or esters of these hydroxy compounds.
[0061] As copolymers, different oxy C 2-4 Copolymers containing alkylene units, etc. The copolymer may be a block copolymer.
[0062] The polyol may be any of aliphatic polyols, alicyclic polyols, aromatic polyols, and heterocyclic polyols. From the viewpoint of facilitating thin spreading of the polymer compound on the lead surface, aliphatic polyols and alicyclic polyols (e.g., polyhydroxycyclohexane, polyhydroxynorbornane) are preferred, and among them, aliphatic polyols are preferred. Examples of aliphatic polyols include aliphatic diols and polyols having a triol or more (e.g., glycerin, trimethylolpropane, pentaerythritol, sugar, or sugar alcohol). Examples of aliphatic diols include alkylene glycols having 5 or more carbon atoms. Examples of alkylene glycols include C5~14 Alkylene glycol or C 5-10 The sugar or sugar alcohol may be, for example, sucrose, erythritol, xylitol, mannitol, or sorbitol. The sugar or sugar alcohol may be either a chain structure or a cyclic structure. In the polyalkylene oxide adduct of the polyol, the alkylene oxide is an oxy-C of the polymer compound. 2-4 Corresponding to an alkylene unit, at least C 2-4 In view of the ease with which the polymer compound has a linear structure, the polyol is preferably a diol.
[0063] The etherified product is the above-mentioned oxy C 2-4 At least some of the terminal -OH groups (composed of a hydrogen atom of the terminal group and an oxygen atom bonded to the hydrogen atom) of the hydroxy compound having a repeating structure of alkylene units are etherified to form -OR 2 Groups, where R 2 is an organic group.) Some or all of the terminals of the polymer compound may be etherified. For example, one terminal of the main chain of a linear polymer compound is an -OH group and the other terminal is an -OR group. 2 It may also be a group.
[0064] The esterified product is the above-mentioned oxy C 2-4 At least some of the terminal -OH groups (composed of a hydrogen atom of the terminal group and an oxygen atom bonded to this hydrogen atom) of a hydroxy compound having a repeating structure of an alkylene unit are esterified to form -OC(=O)-R 3 Groups, where R 3 is an organic group.) Some or all of the terminals of the polymer compound may be esterified. For example, one terminal of the main chain of a linear polymer compound is an -OH group and the other terminal is an -OC(=O)-R 3 It may also be a group.
[0065] organic group R 2 and R 3 Each of the above may be a hydrocarbon group. The hydrocarbon group may have a substituent (e.g., a hydroxy group, an alkoxy group, and / or a carboxy group). The hydrocarbon group may be any of aliphatic, alicyclic, and aromatic. The aromatic hydrocarbon group and the alicyclic hydrocarbon group may have an aliphatic hydrocarbon group (e.g., an alkyl group, an alkenyl group, an alkynyl group) as a substituent. The number of carbon atoms in the aliphatic hydrocarbon group as a substituent may be, for example, 1 to 30, 1 to 20, 1 to 10, 1 to 6, or 1 to 4.
[0066] Examples of the aromatic hydrocarbon group include aromatic hydrocarbon groups having 24 or less carbon atoms (e.g., 6 to 24). The number of carbon atoms in the aromatic hydrocarbon group may be 20 or less (e.g., 6 to 20), 14 or less (e.g., 6 to 14), or 12 or less (e.g., 6 to 12). Examples of the aromatic hydrocarbon group include aryl groups and bisaryl groups. Examples of the aryl group include phenyl groups and naphthyl groups. Examples of the bisaryl group include monovalent groups corresponding to bisarenes. Examples of the bisarenes include biphenyl, bisarylalkanes (e.g., bisC 6-10 Aryl C 1-4 Alkanes (such as 2,2-bisphenylpropane) are examples.
[0067] Examples of the alicyclic hydrocarbon group include alicyclic hydrocarbon groups having 16 or less carbon atoms. The alicyclic hydrocarbon group may be a cross-linked cyclic hydrocarbon group. The number of carbon atoms in the alicyclic hydrocarbon group may be 10 or less or 8 or less. The number of carbon atoms in the alicyclic hydrocarbon group may be, for example, 5 or more, or 6 or more.
[0068] The alicyclic hydrocarbon group may have 5 (or 6) or more and 16 (or less), 5 (or 6) or more and 10 (or less), or 5 (or 6) or more and 8 (or less) carbon atoms.
[0069] Examples of alicyclic hydrocarbon groups include cycloalkyl groups (cyclopentyl, cyclohexyl, cyclooctyl, etc.) and cycloalkenyl groups (cyclohexenyl, cyclooctenyl, etc.). Alicyclic hydrocarbon groups also include hydrogenated products of the above aromatic hydrocarbon groups.
[0070] From the viewpoint of facilitating thin adhesion of the polymer compound to the lead surface, among the hydrocarbon groups, an aliphatic hydrocarbon group is preferred. The aliphatic hydrocarbon group may be saturated or unsaturated. Examples of the aliphatic hydrocarbon group include an alkyl group, an alkenyl group, an alkynyl group, a dienyl group having two carbon-carbon double bonds, and a trienyl group having three carbon-carbon double bonds. The aliphatic hydrocarbon group may be either linear or branched.
[0071] The number of carbon atoms in the aliphatic hydrocarbon group is, for example, 30 or less, and may be 26 or less or 22 or less, 20 or less or 16 or less, 14 or less or 10 or less, or 8 or less or 6 or less. The lower limit of the number of carbon atoms depends on the type of the aliphatic hydrocarbon group, and is 1 or more for alkyl groups, 2 or more for alkenyl groups and alkynyl groups, 3 or more for dienyl groups, and 4 or more for trienyl groups. Among these, alkyl groups and alkenyl groups are preferred from the viewpoint of facilitating thin adhesion of the polymer compound to the lead surface.
[0072] Specific examples of alkyl groups include methyl, ethyl, n-propyl, i-propyl, n-butyl, i-butyl, s-butyl, t-butyl, n-pentyl, neopentyl, i-pentyl, s-pentyl, 3-pentyl, t-pentyl, n-hexyl, 2-ethylhexyl, n-octyl, n-nonyl, n-decyl, i-decyl, undecyl, lauryl (dodecyl), tridecyl, myristyl, pentadecyl, cetyl, heptadecyl, stearyl, icosyl, henicosyl, and behenyl.
[0073] Specific examples of the alkenyl group include vinyl, 1-propenyl, allyl, cis-9-heptadecen-1-yl, palmitoleyl, and oleyl. 2-30 Alkenyl group or C 2-26 may be an alkenyl group, C 2-22 Alkenyl group or C 2-20 may be an alkenyl group, C 10-20 It may be an alkenyl group.
[0074] Among the polymer compounds, oxy C 2-4 Ethers of hydroxy compounds with repeating alkylene units and oxy C 2-4 It is preferable to use at least one selected from the group consisting of esters of hydroxy compounds having a repeating structure of alkylene units, because it is easy to obtain a higher high-temperature float life performance while maintaining a high HR discharge performance. Among such polymer compounds, a polymer compound having a repeating structure of oxypropylene units or a polymer compound having a repeating structure of oxyethylene units is preferable.
[0075] The polymer compound may have one or more hydrophobic groups. Examples of the hydrophobic group include, among the above-mentioned hydrocarbon groups, aromatic hydrocarbon groups, alicyclic hydrocarbon groups, and long-chain aliphatic hydrocarbon groups. Examples of the long-chain aliphatic hydrocarbon group include, among the above-mentioned aliphatic hydrocarbon groups (alkyl groups, alkenyl groups, etc.), aliphatic hydrocarbon groups having 8 or more carbon atoms, preferably 12 or more, and more preferably 16 or more. Among them, a polymer compound having a long-chain aliphatic hydrocarbon group is advantageous in ensuring high HR discharge performance because it is less likely to cause excessive adsorption to lead and can more effectively suppress uneven distribution of the polymer compound. The polymer compound may be a polymer compound in which at least one of the hydrophobic groups is a long-chain aliphatic hydrocarbon group. The carbon number of the long-chain aliphatic hydrocarbon group may be 30 or less, 26 or less, or 22 or less.
[0076] The carbon number of the long-chain aliphatic hydrocarbon group may be 8 or more (or 12 or more) and 30 or less, 8 or more (or 12 or more) and 26 or less, 8 or more (or 12 or more) and 22 or less, 10 or more and 30 or less (or 26 or less), or 10 or more and 22 or less.
[0077] Among the polymer compounds, a polymer compound having a hydrophilic group and a hydrophobic group corresponds to a nonionic surfactant. The repeating structure of an oxyethylene unit exhibits high hydrophilicity and can be a hydrophilic group in a nonionic surfactant. Therefore, it is preferable that the above-mentioned polymer compound having a hydrophobic group contains a repeating structure of an oxyethylene unit. Such a polymer compound can selectively adsorb lead while suppressing excessive coverage of the lead surface due to the balance between hydrophobicity and high hydrophilicity due to the repeating structure of the oxyethylene unit, and uneven distribution is suppressed, so that a higher high-temperature float life performance can be ensured while maintaining a high HR discharge performance. Such a polymer compound can ensure high adsorption to lead even if it has a relatively low molecular weight (for example, Mn is 1000 or less).
[0078] Among the above polymer compounds, polyoxypropylene-polyoxyethylene block copolymers, etherified products of hydroxy compounds having a repeating structure of oxyethylene units, and esterified products of hydroxy compounds having a repeating structure of oxyethylene units correspond to nonionic surfactants.
[0079] In a polyoxypropylene-polyoxyethylene block copolymer, the repeating structure of the oxyethylene unit corresponds to the hydrophilic group, and the repeating structure of the oxypropylene unit corresponds to the hydrophobic group. Such a copolymer is also included in the polymer compound having a hydrophobic group.
[0080] Examples of polymer compounds having a hydrophobic group and containing a repeating structure of oxyethylene units include etherified polyethylene glycol (such as alkyl ethers), esterified polyethylene glycol (such as carboxylates), etherified polyethylene oxide adducts of the above polyols (such as alkyl ethers), and esterified polyethylene oxide adducts of the above polyols (such as triols or higher polyols) (such as carboxylates). Specific examples of such polymer compounds include polyethylene glycol oleate, polyethylene glycol dioleate, polyethylene glycol dilaurate, polyethylene glycol distearate, polyoxyethylene coconut oil fatty acid sorbitan, polyoxyethylene sorbitan oleate, polyoxyethylene sorbitan stearate, polyoxyethylene lauryl ether, polyoxyethylene tetradecyl ether, and polyoxyethylene cetyl ether. However, the polymer compounds are not limited to these. Among them, the use of esterified polyethylene glycol and esterified polyethylene oxide adducts of the above polyols can ensure higher charge acceptance and increase the effect of shifting the potential of the electrode plate in the less noble direction, thereby further improving the high-temperature float life performance.
[0081] For polymer compounds classified as surfactants, from the viewpoint of increasing the effect of shifting the potential of the electrode plate in the less noble direction and easily ensuring higher high-temperature float life performance, the HLB of the polymer compound is preferably 4 or more, more preferably 4.3 or more. From the viewpoint of easily ensuring higher charge acceptance and thus higher high-temperature float life performance, the HLB of the polymer compound is preferably 18 or less, more preferably 10 or less or 9 or less, and even more preferably 8.5 or less.
[0082] The HLB of the polymer compound may be 4 or more (or 4.3 or more) and 18 or less, or 4 or more (or 4.3 or more) and 10 or less. From the viewpoint of ensuring higher high-temperature float life performance, the HLB of the polymer compound is preferably 4 or more (or 4.3 or more) and 9 or less, or 4 or more (or 4.3 or more) and 8.5 or less.
[0083] HLB is an abbreviation for Hydrophile Lipophile Balance, and is a value that indicates the balance between hydrophobicity and hydrophilicity of a surfactant (mainly a nonionic surfactant).
[0084] Oxy C 2-4 It is also preferable that the repeating structure of the alkylene contains at least a repeating structure of an oxypropylene unit. In this case, the charge acceptance tends to be lower than when the repeating structure of an oxyethylene unit is contained, but even in this case, it is possible to ensure higher high-temperature float life performance while maintaining high HR discharge performance. The polymer compound containing the oxypropylene unit is 1 In the chemical shift of the H-NMR spectrum, peaks due to -CH< and -CH2- of the oxypropylene unit are present in the range of 3.2 ppm to 3.8 ppm. The peaks are split due to differences in electron density around the nuclei of the hydrogen atoms in these groups. Such a polymer compound is 1 In the chemical shift of the H-NMR spectrum, for example, there are peaks in the range of 3.2 ppm to 3.42 ppm and in the range of more than 3.42 ppm to 3.8 ppm. The peak in the range of 3.2 ppm to 3.42 ppm is derived from -CH2-, and the peak in the range of more than 3.42 ppm to 3.8 ppm is derived from -CH< and -CH2-.
[0085] Examples of polymer compounds containing at least a repeating structure of oxypropylene units include polypropylene glycol, copolymers containing a repeating structure of oxypropylene units, polypropylene oxide adducts of the above polyols, and etherified or esterified products thereof. Examples of copolymers include oxypropylene-oxyalkylene copolymers (wherein the oxyalkylene is a C alkylene other than oxypropylene). 2-4 Examples of the oxypropylene-oxyalkylene copolymer include oxypropylene-oxyethylene copolymer and oxypropylene-oxytrimethylene copolymer. The oxypropylene-oxyalkylene copolymer may be called polyoxypropylene-polyoxyalkylene copolymer (for example, polyoxypropylene-polyoxyethylene copolymer). The oxypropylene-oxyalkylene copolymer may be a block copolymer (for example, polyoxypropylene-polyoxyethylene block copolymer). Examples of the etherified product include polypropylene glycol alkyl ether and alkyl ether of oxypropylene-oxyalkylene copolymer (alkyl ether of polyoxypropylene-polyoxyethylene copolymer, etc.). Examples of the esterified product include polypropylene glycol ester of carboxylic acid and carboxylic acid ester of oxypropylene-oxyalkylene copolymer (carboxylic acid ester of polyoxypropylene-polyoxyethylene copolymer, etc.).
[0086] Examples of polymer compounds containing at least a repeating structure of oxypropylene units include polypropylene glycol, polyoxypropylene-polyoxyethylene copolymers (polyoxypropylene-polyoxyethylene block copolymers, etc.), polypropylene glycol alkyl ethers (see above R 2 alkyl ethers (methyl ether, ethyl ether, butyl ether, etc.) in which R is an alkyl having 10 or less carbon atoms (or 8 or less or 6 or less), polyoxyethylene-polyoxypropylene alkyl ethers (the above R 2alkyl ethers (butyl ether, hydroxyhexyl ether, etc.) in which R is an alkyl having 10 or less carbon atoms (or 8 or less or 6 or less), polypropylene glycol carboxylates (the above R 3 Examples of the polymer compound include polypropylene glycol carboxylates (such as polypropylene glycol acetates) in which the alkyl group has 10 or less carbon atoms (or 8 or less or 6 or less), and polypropylene oxide adducts of triol or higher polyols (such as polypropylene oxide adducts of glycerin). However, the polymer compound is not limited to these.
[0087] The polymer compound is preferably oxy-C, in order to increase the adsorption of the polymer compound to lead and to facilitate the polymer compound to have a linear structure. 2-4 It is preferable that the polymer compound contains a large number of alkylene units. Such a polymer compound contains, for example, an oxygen atom bonded to the end group and a -CH2- group and / or a -CH< group bonded to the oxygen atom. 1 In the H-NMR spectrum, the integral value of the peak at 3.2 ppm to 3.8 ppm accounts for a large proportion of the total integral value of this peak, the integral value of the peak of the hydrogen atom of the -CH2- group, and the integral value of the peak of the hydrogen atom of the -CH< group. This proportion is, for example, 50% or more, and may be 80% or more. From the viewpoint of easily ensuring higher high-temperature float life performance while maintaining high HR discharge performance, the above proportion is preferably 85% or more, and more preferably 90% or more. For example, when a polymer compound has an -OH group at its terminal and has a -CH2- group and / or a -CH< group bonded to the oxygen atom of the -OH group, 1 In the H-NMR spectrum, the peaks of the hydrogen atoms of the -CH2- group and the -CH< group have chemical shifts in the range of more than 3.8 ppm to 4.0 ppm.
[0088] The negative electrode material may contain one type of polymer compound or two or more types of polymer compounds.
[0089] The polymer compound may, for example, contain a compound with Mn of 5 million or less, may contain a compound with Mn of 1 million or less or 100,000 or less, may contain a compound with Mn of 20,000 or less or 10,000 or less, or may contain a compound with Mn of 5,000 or less. From the viewpoint of ensuring higher high-temperature float life performance by increasing the charge acceptance, the polymer compound preferably contains a compound with Mn of 4,000 or less, and may contain a compound with Mn of 3,700 or less or 3,500 or less. From the viewpoint of obtaining higher high-temperature float life performance by increasing the effect of shifting the potential of the electrode plate in the less noble direction, the Mn of such a compound may be 300 or more or 400 or more, 500 or more, or 800 or more or 1,000 or more. As the polymer compound, two or more compounds with different Mn may be used. In other words, the polymer compound may be a polymer compound having multiple Mn peaks in the molecular weight distribution.
[0090] The Mn of the above compounds is 300 to 5 million (or 1 million or less), 400 to 5 million (or 1 million or less), 500 to 5 million (or 1 million or less), 800 to 5 million (or 1 million or less), 1000 to 5 million (or 1 million or less), 300 to 100,000 (or 20,000 or less), 400 to 100,000 (or 20,000 or less), 500 to 100,000 (or 20,000 or less), 800 to 100,000 (or 20,000 or less), 1000 to 100,000 (or 20,000 or less), 300 to 10,000 (or 5,000 or less), 400 to 100,000 (or 20,000 or less), 000 or less (or 5000 or less), 500 or more and 10000 or less (or 5000 or less), 800 or more and 10000 or less (or 5000 or less), 1000 or more and 10000 or less (or 5000 or less), 300 or more and 4000 or less (or 3700 or less), 400 or more and 4000 or less (or 3700 or less), 500 or more and 4000 or less (or 3700 or less), 800 or more and 4000 or less (or 3700 or less), 1000 or more and 4000 or less (or 3700 or less), 300 or more (or 400 or more) and 3500 or less, 500 or more (or 800 or more) and 3500 or less, or 1000 or more and 3500 or less.
[0091] The content of the polymer compound in the negative electrode material is, for example, 3 ppm or more by mass. From the viewpoint of easily obtaining higher high-temperature float life performance by increasing the effect of shifting the potential of the electrode plate in the less noble direction, the content of the polymer compound in the negative electrode material is preferably 5 ppm or more by mass, and may be 80 ppm or more or 100 ppm or more. The content of the polymer compound in the negative electrode material is, for example, 5000 ppm or less by mass, and may be 3000 ppm or less. From the viewpoint of easily obtaining higher high-temperature float life performance by obtaining higher charge acceptance, the content of the polymer compound in the negative electrode material is preferably 2000 ppm or less or 1000 ppm or less, and may be less than 1000 ppm, 700 ppm or less, or 500 ppm or less.
[0092] The content of polymer compounds in the negative electrode material is, by mass, 3 ppm or more (or 5 ppm or more) and 5000 ppm or less, 3 ppm or more (or 5 ppm or more) and 3000 ppm or less, 3 ppm or more (or 5 ppm or more) and 2000 ppm or less, 3 ppm or more (or 5 ppm or more) and 1000 ppm or less, 3 ppm or more (or 5 ppm or more) and less than 1000 ppm, 3 ppm or more (or 5 ppm or more) and 700 ppm or less, 3 ppm or more (or 5 ppm or more) and 500 ppm or less, It may be 80 ppm or more (or 100 ppm or more) but 5000 ppm or less, 80 ppm or more (or 100 ppm or more) but 3000 ppm or less, 80 ppm or more (or 100 ppm or more) but 2000 ppm or less, 80 ppm or more (or 100 ppm or more) but 1000 ppm or less, 80 ppm or more (or 100 ppm or more) but less than 1000 ppm, 80 ppm or more (or 100 ppm or more) but 700 ppm or less, or 80 ppm or more (or 100 ppm or more) but 500 ppm or less.
[0093] (Organic shrink-proofing agent) An organic shrinkage inhibitor is an organic compound that has a function of suppressing the shrinkage of lead, which is a negative electrode active material, when a lead-acid battery is repeatedly charged and discharged. Organic shrinkage inhibitors are generally broadly classified into lignin compounds and synthetic organic shrinkage inhibitors. It can also be said that a synthetic organic shrinkage inhibitor is an organic shrinkage inhibitor other than a lignin compound. Examples of organic shrinkage inhibitors contained in the negative electrode material include lignin compounds and synthetic organic shrinkage inhibitors. The negative electrode material may contain one type of organic shrinkage inhibitor, or two or more types of organic shrinkage inhibitors.
[0094] Examples of the lignin compound include lignin and lignin derivatives. Examples of the lignin derivatives include lignin sulfonic acid or salts thereof (alkali metal salts (sodium salts, etc.)).
[0095] The synthetic organic shrink-proofing agent is an organic polymer containing elemental sulfur, and generally contains multiple aromatic rings in the molecule and elemental sulfur as a sulfur-containing group. Among the sulfur-containing groups, sulfonic acid groups or sulfonyl groups, which are stable, are preferred. The sulfonic acid groups may exist in the acid form or in the salt form such as Na salt.
[0096] At least a lignin compound may be used as the organic shrinkage inhibitor. When a lignin compound is used, the charge acceptance is likely to be lower than when a synthetic organic shrinkage inhibitor is used. However, when the negative electrode material contains a specific polymer compound, the decrease in charge acceptance is suppressed even when a lignin compound is used as the organic shrinkage inhibitor.
[0097] As the organic shrink-proofing agent, it is also preferable to use a condensation product containing at least an aromatic compound unit. For example, such a condensation product may be a condensation product of an aromatic compound with an aldehyde compound (at least one selected from the group consisting of aldehydes (e.g., formaldehyde) and condensates thereof). The organic shrink-proofing agent may contain one type of aromatic compound unit, or may contain two or more types of aromatic compound units. The aromatic compound unit refers to a unit derived from an aromatic compound incorporated in the condensation product.
[0098] Examples of the aromatic rings that aromatic compounds have include benzene rings and naphthalene rings. When aromatic compounds have multiple aromatic rings, the multiple aromatic rings may be linked by direct bonds or linking groups (e.g., alkylene groups (including alkylidene groups), sulfone groups) and the like. Examples of such structures include bisarene structures (biphenyl, bisphenylalkane, bisphenylsulfone, etc.). Examples of aromatic compounds include compounds having the above aromatic rings and at least one selected from the group consisting of hydroxyl groups and amino groups. The hydroxyl group or amino group may be directly bonded to the aromatic ring, or may be bonded as an alkyl chain having a hydroxyl group or amino group. The hydroxyl group also includes salts of the hydroxyl group (-OMe). The amino group also includes salts of the amino group (specifically, salts with anions). Examples of Me include alkali metals (Li, K, Na, etc.) and metals of Group 2 of the periodic table (Ca, Mg, etc.).
[0099] As the aromatic compound, bisarene compounds [bisphenol compounds, hydroxybiphenyl compounds, bisarene compounds having an amino group (bisarylalkane compounds having an amino group, bisarylsulfone compounds having an amino group, biphenyl compounds having an amino group, etc.), hydroxyarene compounds (hydroxynaphthalene compounds, phenol compounds, etc.), aminoarene compounds (aminonaphthalene compounds, aniline compounds (aminobenzenesulfonic acid, alkylaminobenzenesulfonic acid, etc.)), etc.] are preferred. The aromatic compound may further have a substituent. The organic shrinkage inhibitor may contain one or more of the residues of these compounds. As the bisphenol compound, bisphenol A, bisphenol S, bisphenol F, etc. are preferred.
[0100] The condensate preferably contains at least a unit of an aromatic compound having a sulfur-containing group. In particular, the use of a condensate containing at least a unit of a bisphenol compound having a sulfur-containing group is advantageous in terms of ensuring higher charge acceptance.
[0101] The sulfur-containing group may be directly bonded to an aromatic ring contained in the compound, or may be bonded to the aromatic ring as an alkyl chain having a sulfur-containing group. The sulfur-containing group is not particularly limited, and examples thereof include a sulfonyl group, a sulfonic acid group, and salts thereof.
[0102] Also, as the organic shrink-proofing agent, for example, at least one condensate containing at least one selected from the group consisting of the above-mentioned bisarene compound units and monocyclic aromatic compound units (hydroxyarene compounds and / or aminoarene compounds, etc.) may be used. The organic shrink-proofing agent may at least contain a condensate containing a bisarene compound unit and a monocyclic aromatic compound unit (particularly, a hydroxyarene compound). Such a condensate may be a condensate of a bisarene compound and a monocyclic aromatic compound with an aldehyde compound. As the hydroxyarene compound, a phenolsulfonic acid compound (such as phenolsulfonic acid or a substituted product thereof) is preferable. As the aminoarene compound, aminobenzenesulfonic acid, alkylaminobenzenesulfonic acid, etc. are preferable. As the monocyclic aromatic compound, a hydroxyarene compound is preferable.
[0103] The content of the organic shrinkage inhibitor contained in the negative electrode material is, for example, 0.005% by mass or more, and may be 0.01% by mass or more. When the content of the organic shrinkage inhibitor is in such a range, high HR discharge performance can be ensured. The content of the organic shrinkage inhibitor is, for example, 1.0% by mass or less, and may be 0.5% by mass or less, or may be 0.2% by mass or less.
[0104] The content of the organic shrinkage inhibitor in the negative electrode material may be 0.005% by mass or more (or 0.01% by mass or more) and 1.0% by mass or less, 0.005% by mass or more (or 0.01% by mass or more) and 0.5% by mass or less, or 0.005% by mass or more (or 0.01% by mass or more) and 0.2% by mass or less.
[0105] (carbonaceous material) Carbon black, graphite, hard carbon, soft carbon, etc. can be used as the carbonaceous material contained in the negative electrode material. Examples of carbon black include acetylene black, furnace black, lamp black, etc. Furnace black also includes Ketjen Black (trade name). Graphite may be any carbonaceous material containing a graphite-type crystal structure, and may be either artificial graphite or natural graphite. The negative electrode material may contain one type of carbonaceous material, or may contain two or more types.
[0106] The content of the carbonaceous material in the negative electrode material is, for example, 0.05 mass% or more, and may be 0.10 mass% or more.The content of the carbonaceous material is, for example, 5 mass% or less, and may be 3 mass% or less.
[0107] The content of the carbonaceous material in the negative electrode material may be 0.05% by mass to 5% by mass, 0.05% by mass to 3% by mass, 0.10% by mass to 5% by mass, or 0.10% by mass to 3% by mass.
[0108] (Barium Sulfate) The content of barium sulfate in the negative electrode material is, for example, 0.05% by mass or more, and may be 0.10% by mass or more. The content of barium sulfate in the negative electrode material is, for example, 3% by mass or less, and may be 2% by mass or less.
[0109] The content of barium sulfate in the negative electrode material may be from 0.05 to 3% by mass, from 0.05 to 2% by mass, from 0.10 to 3% by mass, or from 0.10 to 2% by mass.
[0110] (Analysis of the components of negative electrode materials) The method for analyzing the components of the negative electrode material is described below. Prior to measurement or analysis, a fully charged lead-acid battery is disassembled to obtain a negative plate to be analyzed. The obtained negative plate is washed with water to remove sulfuric acid from the negative plate. The washing is performed by pressing a pH test paper against the washed surface of the negative plate until it is confirmed that the color of the test paper does not change. However, the washing time is within 2 hours. The washed negative plate is dried at 60±5°C for about 6 hours in a reduced pressure environment. If the negative plate contains an adhesive material after drying, the adhesive material is removed by peeling. Next, a sample (hereinafter referred to as sample A) is obtained by separating the negative electrode material from the negative plate. Sample A is crushed as necessary and subjected to analysis.
[0111] (1) Analysis of polymer compounds (1-1) Qualitative analysis of polymer compounds (a) OxyC 2-4 Analysis of alkylene units A crushed sample A is used. 150.0±0.1 mL of chloroform is added to 100.0±0.1 g of sample A, and the mixture is stirred at 20±5°C for 16 hours to extract the polymer compound. The solid content is then removed by filtration. The polymer compound is identified by obtaining information from at least one of infrared spectroscopy, ultraviolet-visible absorption spectroscopy, NMR spectroscopy, LC-MS, and pyrolysis GC-MS for the chloroform solution in which the polymer compound obtained by extraction is dissolved or the polymer compound obtained by drying the chloroform solution.
[0112] The chloroform soluble matter is recovered by distilling off the chloroform under reduced pressure from the chloroform solution in which the polymer compound obtained by extraction is dissolved. The chloroform soluble matter is dissolved in deuterated chloroform and then subjected to the following conditions: 1 1H-NMR spectrum is measured. 1 From the H-NMR spectrum, a peak with a chemical shift in the range of 3.2 ppm to 3.8 ppm is confirmed. Also, from the peak in this range, oxy C2-4 Identify the type of alkylene unit.
[0113] Equipment: AL400 nuclear magnetic resonance equipment manufactured by JEOL Ltd. Observation frequency: 395.88MHz Pulse width: 6.30μs Pulse repetition time: 74.1411 seconds Accumulation count: 32 Measurement temperature: room temperature (20~35℃) Standard: 7.24ppm Sample tube diameter: 5mm
[0114] 1 From the H-NMR spectrum, the integral value (V1) of the peaks present in the chemical shift range of 3.2 ppm to 3.8 ppm is calculated. In addition, for each of the hydrogen atoms of the -CH2- group and -CH< group bonded to the oxygen atom bonded to the terminal group of the polymer compound, 1 The sum (V2) of the integral values of the peaks in the H-NMR spectrum is calculated. Then, from V1 and V2, the percentage of V1 in the sum of V1 and V2 (=V1 / (V1+V2)×100(%)) is calculated.
[0115] In addition, in the qualitative analysis, 1 When calculating the integral value of a peak in a H-NMR spectrum, 1 In the H-NMR spectrum, two points without significant signals are determined so as to sandwich the corresponding peak, and each integral value is calculated using a straight line connecting these two points as a baseline. For example, for a peak that exists in a chemical shift range of 3.2 ppm to 3.8 ppm, a straight line connecting two points on the spectrum between 3.2 ppm and 3.8 ppm is used as the baseline. For example, for a peak that exists in a chemical shift range of more than 3.8 ppm to 4.0 ppm, a straight line connecting two points on the spectrum between 3.8 ppm and 4.0 ppm is used as the baseline.
[0116] (b) Analysis of hydrophobic groups in esterified products When the polymer compound is an ester of a hydroxy compound, a predetermined amount of the polymer compound obtained by drying the chloroform solution in which the polymer compound obtained by extraction is dissolved in (a) is collected, and an aqueous potassium hydroxide solution is added. This causes the ester to be saponified, producing a fatty acid potassium salt and a hydroxy compound. The aqueous potassium solution is added until the saponification is complete. The fatty acid potassium salt is converted to a fatty acid methyl ester by adding and mixing a solution of methanol and boron trifluoride to the resulting mixture. The resulting mixture is analyzed by pyrolysis GC-MS under the following conditions to identify the hydrophobic group contained in the ester. Analytical equipment: Shimadzu Corporation, high-performance general-purpose gas chromatogram GC-2014 Column: DEGS (diethylene glycol succinate) 2.1m Oven temperature: 180~120℃ Inlet temperature: 240℃ Detector temperature: 240℃ Carrier gas: He (flow rate: 50 mL / min) Injection volume: 1μL~2μL
[0117] (c) Analysis of hydrophobic groups in etherified products When the polymer compound is an etherified product of a hydroxy compound, a predetermined amount of the polymer compound obtained by drying the chloroform solution in which the polymer compound obtained by extraction is dissolved in (a) is collected and hydrogen iodide is added. This converts the organic group (the above-mentioned R 3 ) corresponding to the iodide (R 3 I) is generated and oxy C 2-4 Diiodo C corresponding to the alkylene unit 2-4 Alkanes are produced. The hydrogen iodide is converted to etherified iodide and diiodo C. 2-4 Add a sufficient amount of ether to complete the conversion to an alkane. The resulting mixture is analyzed by pyrolysis GC-MS under the same conditions as in (b) above to identify the hydrophobic group contained in the etherified product.
[0118] (1-2) Quantitative analysis of polymer compounds The appropriate amount of the chloroform soluble matter was measured with an accuracy of ±0.0001 g. r (g) Dissolve in deuterated chloroform together with tetrachloroethane (TCE), 1 Measure the H-NMR spectrum. The integral value (S a ) and the integral value of the peak due to TCE (S r ) and calculate the mass-based content C of the polymer compound in the negative electrode material from the following formula: n Calculate the ppm.
[0119] C n =S a / S r ×N r / N a ×M a / M r ×m r / m×1000000 (In the formula, M a The molecular weight of the structure that shows a peak in the chemical shift range of 3.2 to 3.8 ppm (more specifically, oxy C 2-4 (the molecular weight of the repeating structure of alkylene units) and N a is the number of hydrogen atoms attached to the carbon atoms in the main chain of the repeating unit. r、 M r are the number of hydrogen atoms contained in the molecule of the reference material, the molecular weight of the reference material, and m (g) is the mass of the negative electrode material used for extraction.) In addition, the standard substance in this analysis is TCE, so N r =2, M r = 168. Also, m = 100.
[0120] For example, if the polymer compound is polypropylene glycol, M a is 58, and N a is 3. If the polymer compound is polyethylene glycol, M a is 44, and N a is 4. In the case of copolymers, N aand M. a are the N of each monomer unit, a Value and M a The value is calculated by averaging the molar ratio (mol %) of each monomer unit contained in the repeating structure.
[0121] In addition, in the quantitative analysis, 1 The integral value of the peak in the H-NMR spectrum is determined using data processing software “ALICE” manufactured by JEOL Ltd.
[0122] (1-3) Mn measurement of polymer compounds Using the above chloroform solubles, GPC measurement of the polymer compound is carried out using the following apparatus under the following conditions. Separately, a calibration curve (calibration curve) is created from a plot of Mn of the standard substance versus elution time. Based on this calibration curve and the GPC measurement results of the polymer compound, the Mn of the polymer compound is calculated. However, esterified or etherified products may be in a decomposed state in the chloroform solubles.
[0123] Analysis system: 20A system (Shimadzu Corporation) Column: Two GPC KF-805L (Shodex) columns connected in series Column temperature: 30℃±1℃ Mobile phase: Tetrahydrofuran Flow rate: 1mL / min. Concentration: 0.20% by mass Injection volume: 10μL Standard substance: polyethylene glycol (Mn=2,000,000, 200,000, 20,000, 2,000, 200) Detector: Differential refractive index detector (Shodex RI-201H)
[0124] (2) Analysis of organic shrinkage inhibitors (2-1) Qualitative analysis of organic shrinkage inhibitors in negative electrode materials The ground sample A is immersed in a 1 mol / L aqueous solution of sodium hydroxide to extract the organic shrink-proofing agent. Next, insoluble components are removed from the extract by filtration, and the resulting solution is desalted, concentrated, and dried. Desalting is performed using a desalting column, by passing the solution through an ion exchange membrane, or by placing the solution in a dialysis tube and immersing it in distilled water. By drying this, a powder sample of the organic shrink-proofing agent (hereinafter referred to as sample B) is obtained.
[0125] The type of organic shrinkage inhibitor is identified by combining information obtained from the following: an infrared spectrum measured using sample B of the organic shrinkage inhibitor obtained in this manner; an ultraviolet-visible absorption spectrum measured using an ultraviolet-visible spectrometer after diluting sample B with distilled water or the like; an NMR spectrum of a solution obtained by dissolving sample B in a specified solvent such as heavy water; or information obtained from pyrolysis GC-MS, which can provide information on the individual compounds that make up the substance.
[0126] (2-2) Quantitative determination of organic shrinkage inhibitor content in negative electrode material As in the above (2-1), the insoluble components of the separated material containing the organic shrinkage inhibitor are removed by filtration to obtain a solution. The ultraviolet-visible absorption spectrum of each of the obtained solutions is measured. The content of each organic shrinkage inhibitor in the negative electrode material is determined using the intensity of the peak characteristic of each organic shrinkage inhibitor and a calibration curve prepared in advance.
[0127] In addition, when a lead-acid battery with an unknown content of organic shrink-proofing agent is obtained and the content of the organic shrink-proofing agent is measured, the structural formula of the organic shrink-proofing agent cannot be precisely specified, so the same organic shrink-proofing agent cannot be used for the calibration curve. In this case, a calibration curve is created using the organic shrink-proofing agent extracted from the negative electrode of the battery and a separately available organic polymer that shows similar shapes in the ultraviolet-visible absorption spectrum, infrared spectroscopy spectrum, and NMR spectrum, and the content of the organic shrink-proofing agent is measured using the ultraviolet-visible absorption spectrum.
[0128] (3) Quantitative analysis of carbonaceous materials and barium sulfate Add 50 ml of 20% by mass nitric acid to 10 g of crushed sample A, heat for about 20 minutes, and dissolve the lead components as lead ions. Filter the resulting solution to separate solids such as carbonaceous materials and barium sulfate.
[0129] The obtained solid content is dispersed in water to obtain a dispersion, and then components other than the carbonaceous material and barium sulfate (e.g., reinforcing material) are removed from the dispersion using a sieve. Next, the dispersion is subjected to suction filtration using a membrane filter whose mass has been measured in advance, and the membrane filter together with the filtered sample is dried in a dryer at 110°C ± 5°C. The filtered sample is a mixed sample of the carbonaceous material and barium sulfate. The mass of the membrane filter is subtracted from the total mass of the dried mixed sample (hereinafter referred to as sample C) and the membrane filter to obtain the mass of sample C (M m ) is measured. Sample C is then placed in a crucible together with the membrane filter and incinerated at 1300°C or higher. The remaining residue is barium oxide. The mass of barium oxide is converted to the mass of barium sulfate to obtain the mass of barium sulfate (M B ) is calculated. Mass M m From mass M B The mass of the carbonaceous material is calculated by subtracting the above.
[0130] (others) The negative electrode plate can be formed by applying or filling a negative electrode paste onto a negative electrode current collector, aging and drying to prepare an unformed negative electrode plate, and then chemically forming the unformed negative electrode plate. The negative electrode paste is prepared, for example, by adding water and sulfuric acid (or an aqueous sulfuric acid solution) to lead powder, a polymer compound, and, if necessary, at least one selected from the group consisting of an organic shrinkage inhibitor, a carbonaceous material, and other additives, and kneading the mixture. When aging, it is preferable to age the unformed negative electrode plate at a temperature higher than room temperature and at a high humidity.
[0131] The formation can be carried out by immersing the plate group including the unformed negative plate in an electrolyte containing sulfuric acid in a lead-acid battery container and charging the plate group. However, the formation may be carried out before assembling the lead-acid battery or the plate group. The formation produces spongy lead.
[0132] (Positive plate) The positive electrode plate of the lead-acid battery can be classified into a paste type, a clad type, and the like. Either a paste type or a clad type positive electrode plate may be used. The paste type positive electrode plate includes a positive electrode current collector and a positive electrode material. The configuration of the clad type positive electrode plate is as described above.
[0133] The positive electrode material contained in the positive electrode plate contains a positive electrode active material (lead dioxide or lead sulfate) that develops capacity through an oxidation-reduction reaction. The positive electrode material may contain other additives as necessary.
[0134] The positive electrode current collector may be formed by casting lead (Pb) or a lead alloy, or may be formed by processing a lead sheet or a lead alloy sheet. Examples of the processing method include expanding and punching. It is preferable to use a lattice-shaped current collector as the positive electrode current collector because it is easy to support the positive electrode material.
[0135] The positive electrode current collector may be made of pure lead, but when a lead alloy is used, for example, a Pb-Ca based alloy, a Pb-Sn based alloy, a Pb-Ca-Sn based alloy, etc. may be used. The lead alloy may further contain at least one kind selected from the group consisting of Ba, Ag, Al, Bi, As, Se, Cu, etc. as an additive element.
[0136] The Ca content of the positive electrode current collector or the lead alloy constituting the positive electrode current collector is 0.07% by mass or less, may be 0.06% by mass or less, or may be less than 0.01% by mass. When the Ca content is in such a range, the effect of inhibiting corrosion of the positive electrode current collector during high-temperature float charging by using a polymer compound as the negative electrode material is significantly exhibited. The Ca content may be, for example, 0% by mass or more, or 0.01% by mass or more.
[0137] The Ca content may be 0 mass% or more (or 0.01 mass% or more) and 0.07 mass% or less, 0 mass% or more (or 0.01 mass% or more) and 0.06 mass% or less, or may be 0 mass% or more and less than 0.01 mass%.
[0138] The Sn content of the positive electrode current collector or the lead alloy constituting the positive electrode current collector is, for example, 7% by mass or less, and may be 6% by mass or less or 5% by mass or less. The Sn content is preferably 3% by mass or less. In this case, the effect of reducing the content of Sn-rich β phase with a high corrosion rate is enhanced. The Sn content is more preferably 2% by mass or less or 1.5% by mass or less, and may be 1% by mass or less, 0.05% by mass or less or less than 0.01% by mass. In these cases, the content of Sn-rich β phase with a high corrosion rate is further reduced (preferably, β phase does not exist), which is preferable. The Sn content is, for example, 0% by mass or more, and may be 0.01% by mass or more, or 0.3% by mass or more or 0.5% by mass or more. From the viewpoint of further reducing the corrosion of the positive electrode current collector, the Sn content is preferably 0.8% by mass or more or 1% by mass or more.
[0139] In addition, when the positive electrode current collector contains Ca, the alloy constituting the positive electrode current collector is improved in corrosion resistance by including Sn. For example, when the Ca content in the positive electrode current collector is 0.01 mass% or more, it is preferable that the Sn content of the positive electrode current collector is 0.01 mass% or more. For example, when the lead-acid battery is negative electrode regulated, a higher life performance can be obtained by setting the Ca content to 0.01 mass% or more and 0.06 mass% or less and the Sn content to 0.8 mass% or more (or 1 mass% or more) and 3 mass% or less.
[0140] In addition, when the Ca content in the positive electrode current collector is less than 0.01 mass%, it is preferable that the Sn content in the positive electrode current collector is small from the viewpoint of increasing the effect of reducing the corrosion rate. In this case, the Sn content is preferably 2 mass% or less, more preferably 1.5 mass% or less or 1 mass% or less, and even more preferably 0.05 mass% or less or less than 0.01 mass%. The Sn content is, for example, 0 mass% or more.
[0141] The Sn content in the positive electrode current collector is 0 mass% or more (or 0.01 mass% or more) and 7 mass% or less, 0 mass% or more (or 0.01 mass% or more) and 6 mass% or less, 0 mass% or more (or 0.01 mass% or more) and 5 mass% or less, 0 mass% or more (or 0.01 mass% or more) and 3 mass% or less, 0 mass% or more (or 0.01 mass% or more) and 2 mass% or less, 0 mass% or more (or 0.01 mass% or more) and 1.5 mass% or less, 0 mass% or more (or 0.01 mass% or more) and 1 mass% or less, 0 mass% or more (or 0.01 mass% or more) and 0.05 mass% or less, 0.3 mass% or more (or 0.5 mass% or more) and 7 mass% or less, 0.3 mass% or more (or 0.5 mass% or more) and 6 mass% or less, 0.3 mass% or more (or 0.5 mass% or more) and 5 mass% The content may be 0.3% by mass or more (or 0.5% by mass or more) but 3% by mass or less, 0.3% by mass or more (or 0.5% by mass or more) but 2% by mass or less, 0.3% by mass or more (or 0.5% by mass or more) but 1.5% by mass or less, 0.3% by mass or more (or 0.5% by mass or more) but 1% by mass or less, 0.8% by mass or more (or 1% by mass or more) but 7% by mass or less, 0.8% by mass or more (or 1% by mass or more) but 6% by mass or less, 0.8% by mass or more (or 1% by mass or more) but 5% by mass or less, 0.8% by mass or more (or 1% by mass or more) but 3% by mass or less, 0.8% by mass or more (or 1% by mass or more) but 2% by mass or less, 0.8% by mass or more (or 1% by mass or more) but 1.5% by mass or less, 0.8% by mass or more and 1% by mass or less, or 0% by mass or more but less than 0.01% by mass.
[0142] The positive electrode current collector may have a surface layer. The surface layer and the inner layer of the positive electrode current collector may have different compositions. The surface layer may be formed on a part of the positive electrode current collector. The surface layer may be formed only on the grid portion, the edge portion, or the frame portion of the positive electrode current collector.
[0143] The area of the positive and negative plates facing each other is 2450 mm 2 / Ah or more. From the viewpoint of improving charge acceptance and ensuring higher high-temperature float life performance, the facing area of the positive electrode plate and the negative electrode plate is set to 3500 mm 2 / Ah or more or 4000mm 2 / Ah or more. The facing area of the positive electrode plate and the negative electrode plate is 6700 mm 2 / Ah or less. From the viewpoint of obtaining a higher high-temperature float life performance by making it easier for the polymer compound to exert its effect in inhibiting the corrosion of the positive electrode current collector, the facing area of the positive electrode plate with the negative electrode plate is 6500 mm 2 / Ah or less is preferable, 6100mm 2 / Ah or less is more preferable. The facing area of the positive electrode plate and the negative electrode plate is 5000 mm 2 / Ah or less or 4000mm 2 / Ah or less may be used.
[0144] In addition, the negative electrode material does not contain a polymer compound, and the facing area of the positive electrode plate and the negative electrode plate is 2450 mm 2 If the capacity is less than 1 / Ah, the lead-acid battery is negatively regulated and the lifespan will end due to the deterioration of the negative electrode material. 2 / Ah or more, the lead-acid battery is positively regulated, and the lifespan is determined by the deterioration of the positive electrode current collector. In other words, the deterioration of the positive electrode current collector has a large effect on the lifespan performance. On the other hand, when the negative electrode material contains a polymer compound, the facing area of the positive electrode plate and the negative electrode plate is 5000 mm 2 / Ah or less (for example, 4000mm 2 / Ah or less), lead-acid batteries are negatively regulated and 5000mm 2 / Ah (for example, 6100 mm 2 / Ah or more), lead-acid batteries are regulated by the positive electrode. Therefore, a polymer compound is used as the negative electrode material, and the facing area of the positive plate and the negative plate is 2450 mm 2 / Ah or more 6700mm 2 / Ah or less, the effect of deterioration of the positive electrode current collector on the life performance can be reduced. Also, the value of the facing area that is the negative electrode restriction can be expanded to the higher value side. Therefore, the life performance on the higher value side of the facing area can be improved.
[0145] The area of the positive and negative plates facing each other is 2450 mm 2 / Ah or more 6700mm2 / Ah or less (or 6500mm 2 / Ah or less), 3500mm 2 / Ah or more 6700mm 2 / Ah or less (or 6500mm 2 / Ah or less), 4000mm 2 / Ah or more 6700mm 2 / Ah or less (or 6500mm 2 / Ah or less), 2450mm 2 / Ah or more (or 3500mm 2 / Ah or more) 6100mm 2 / Ah or less, 4000mm 2 / Ah or more 6100mm 2 / Ah or less, 2450mm 2 / Ah more than 5000mm 2 / Ah or less (or 4000mm 2 / Ah or less), 3500mm 2 / Ah more than 5000mm 2 / Ah or less (or 4000mm 2 / Ah or less), or 4000mm 2 / Ah more than 5000mm 2 / Ah or less.
[0146] The opposing area of the positive electrode plate with the negative electrode plate can be adjusted by adjusting at least one of the number of each electrode plate included in the electrode plate group, the size of each electrode plate (at least one of length, width, and thickness), the filling amount of electrode material, the overpaste amount of electrode material, the design of the current collector (e.g., the thickness of the lattice frame, the number of lattices), and the specific gravity of the electrolyte.
[0147] The ratio of the theoretical amount of electricity of the negative plate to the theoretical amount of electricity of the positive plate (theoretical electricity ratio) is, for example, 0.6 or more. From the viewpoint of obtaining a higher high-temperature float life performance by making it easier to balance the utilization rate of the active material between the positive plate and the negative plate, the theoretical electricity ratio is preferably 0.7 or more. From the viewpoint of obtaining a higher high-temperature float life performance by securing a high discharge capacity at an early stage, the theoretical electricity ratio is preferably 1.3 or less.
[0148] The theoretical electrical ratio can be adjusted, for example, by the amount of electrode material filled in each electrode plate.
[0149] Unformed paste-type positive plates are obtained by filling a positive current collector with a positive paste, aging it, and drying it. The positive paste is prepared by kneading lead powder, additives, water, and sulfuric acid. Unformed clad-type positive plates are formed by filling a porous tube into which a core metal connected by a current collector is inserted with lead powder or lead powder in a slurry form, and connecting multiple tubes with a linking wire. Then, these unformed positive plates are formed to obtain positive plates.
[0150] The formation can be carried out by immersing an electrode plate group including unformed positive plates in an electrolyte solution containing sulfuric acid in a battery container of a lead-acid battery and charging the electrode plate group in this state. However, the formation may also be carried out before assembling the lead-acid battery or the electrode plate group.
[0151] (Quantitative analysis of Ca and Sn in positive electrode current collector) Prior to the quantitative analysis of Ca and Sn, the positive electrode material is removed from the positive plate removed from the lead-acid battery to obtain a positive electrode collector, and a part of the positive electrode collector is collected to prepare a sample for analysis. More specifically, the positive electrode material is vibrated to cause it to fall off from the positive electrode collector, and then the positive electrode material remaining around the positive electrode collector is removed using a ceramic knife, and a part of the part of the positive electrode collector having a metallic luster is collected as a sample. After measuring the mass of the collected sample, it is mixed with tartaric acid and dilute nitric acid to obtain an aqueous solution. Hydrochloric acid is added to the aqueous solution to precipitate lead chloride, and the solution is filtered to collect the filtrate. Using this filtrate, the Ca and Sn contents in the positive electrode collector are determined by the following procedure.
[0152] The amount of Ca and Sn contained in the positive electrode current collector is determined in accordance with lead separation inductively coupled plasma optical emission spectroscopy as described in JIS H2105:1955. More specifically, the Ca concentration and Sn concentration in the filtrate are analyzed by a calibration curve method using an ICP optical emission spectrometer, and the respective contents of Ca and Sn in the positive electrode current collector are determined from the obtained concentrations and the masses of the collected samples. As the ICP optical emission spectrometer, an ICPS-8000 manufactured by Shimadzu Corporation is used.
[0153] (Measurement of the area of the positive electrode facing the negative electrode) The area S (mm2) of the overlapping part of the projection shapes of the part of the positive electrode plate where the positive electrode material exists and the part of the negative electrode plate where the negative electrode material exists, projected in the thickness direction of the electrode plate, is 2 ) is calculated. For each surface of the positive plate facing the negative plate in the plate group, the area S is calculated, and the areas S of all the facing surfaces are summed up. If the lead-acid battery has multiple plate groups, the total value of the areas S of the positive plates facing the negative plate is calculated for all the plate groups. In addition, the 10-hour rate capacity (Ah) of the lead-acid battery is measured separately. The total value of the areas S of the lead-acid battery (mm 2 ) by the 10-hour capacity (Ah), the facing area (mm2) of the positive plate and the negative plate per 10-hour capacity of 1 Ah is calculated. 2 / Ah) is required.
[0154] (Measurement of the theoretical electrical charge of each plate) Positive electrode material is collected from all positive plates contained in the lead-acid battery, and the mass (g) of the entire positive electrode material is measured. This mass is multiplied by 0.86 to determine the amount of lead (g) contained in the entire positive electrode material. In a similar manner to the case of the positive plates, negative electrode material is collected from all negative plates contained in the lead-acid battery, and the mass (g) of the entire negative electrode material is measured. This mass is multiplied by 0.99 to determine the amount of lead (g) contained in the entire negative electrode material. The theoretical amount of electricity for each plate is calculated by multiplying the amount of lead contained in each electrode material by the electrical capacity of 0.2587 Ah per gram of Pb atoms.
[0155] (Separator) A separator may be disposed between the negative electrode plate and the positive electrode plate, and may be made of at least one material selected from a nonwoven fabric and a microporous membrane.
[0156] A nonwoven fabric is a mat in which fibers are intertwined without being woven, and is mainly composed of fibers. For example, 60% or more by mass of the nonwoven fabric is made of fibers. As the fibers, glass fibers, polymer fibers (polyolefin fibers, acrylic fibers, polyester fibers (polyethylene terephthalate fibers, etc.), pulp fibers, etc. can be used. Among them, glass fibers are preferable. The nonwoven fabric may contain components other than fibers (for example, acid-resistant inorganic powder, polymers as binders), etc.
[0157] On the other hand, a microporous membrane is a porous sheet mainly composed of components other than fiber components, and can be obtained, for example, by extruding a composition containing a pore-forming agent into a sheet, and then removing the pore-forming agent to form pores. The microporous membrane is preferably made of an acid-resistant material, and a microporous membrane mainly composed of a polymer component is preferred. The polymer component is preferably polyolefin (polyethylene, polypropylene, etc.). The pore-forming agent can be at least one selected from the group consisting of polymer powder and oil.
[0158] The separator may be, for example, composed of only a nonwoven fabric or only a microporous membrane. Furthermore, the separator may be, as necessary, a laminate of a nonwoven fabric and a microporous membrane, a laminate of different or the same materials, or a laminate of different or the same materials with recesses and projections interlocked.
[0159] The separator may be in a sheet shape or may be formed in a bag shape. A sheet-shaped separator may be sandwiched between the positive electrode plate and the negative electrode plate. Also, the electrode plate may be sandwiched between a folded sheet-shaped separator. In this case, the positive electrode plate sandwiched between the folded sheet-shaped separator and the negative electrode plate sandwiched between the folded sheet-shaped separator may be stacked, or one of the positive electrode plate and the negative electrode plate may be sandwiched between the folded sheet-shaped separator and stacked with the other electrode plate. Also, the sheet-shaped separator may be folded into a bellows shape, and the positive electrode plate and the negative electrode plate may be sandwiched between the bellows-shaped separator so that the separator is interposed between them. When a separator folded like an accordion is used, the separator may be arranged so that the folded portion is along the horizontal direction of the lead-acid battery (for example, so that the folded portion is parallel to the horizontal direction) or along the vertical direction (for example, so that the folded portion is parallel to the vertical direction). In a separator folded like an accordion, recesses are formed alternately on both main surfaces of the separator. Since the upper portions of the positive and negative plates usually have lugs, when the separator is arranged so that the folded portion is along the horizontal direction of the lead-acid battery, the positive and negative plates are arranged only in the recesses on one main surface side of the separator (that is, a double separator is interposed between the adjacent positive and negative plates). When the separator is arranged so that the folded portion is aligned with the vertical direction of the lead-acid battery, the positive electrode plate can be accommodated in the recess on one main surface side, and the negative electrode plate can be accommodated in the recess on the other main surface side (that is, a single layer of separator can be interposed between adjacent positive and negative electrode plates.) When a pouch-shaped separator is used, the pouch-shaped separator may accommodate either the positive or negative electrode plate.
[0160] (electrolyte) The electrolyte is an aqueous solution containing sulfuric acid, which may be gelled as necessary. The electrolyte may contain the above-mentioned polymer compound.
[0161] The electrolytic solution may contain cations (e.g., metal cations) and / or anions (e.g., anions other than sulfate anions (e.g., phosphate ions)) as necessary. Examples of metal cations include at least one selected from the group consisting of Na ions, Li ions, Mg ions, and Al ions.
[0162] The specific gravity of the electrolyte in a fully charged lead-acid battery at 20° C. is, for example, 1.20 or more, and may be 1.25 or more. The specific gravity of the electrolyte at 20° C. is 1.35 or less, and preferably 1.32 or less.
[0163] The specific gravity of the electrolyte at 20° C. may be 1.20 or more and 1.35 or less, 1.20 or more and 1.32 or less, 1.25 or more and 1.35 or less, or 1.25 or more and 1.32 or less.
[0164] (others) The lead-acid battery can be obtained by a manufacturing method including a step of housing a plate group and an electrolyte in a cell chamber of a battery case. Each cell of the lead-acid battery includes a plate group and an electrolyte housed in each cell chamber. The plate group is assembled by stacking a positive electrode plate, a negative electrode plate, and a separator such that the separator is interposed between the positive electrode plate and the negative electrode plate prior to housing in the cell chamber. The positive electrode plate, the negative electrode plate, the electrolyte, and the separator are each prepared prior to assembling the plate group. The manufacturing method of the lead-acid battery may include a step of chemically forming at least one of the positive electrode plate and the negative electrode plate, as necessary, after the step of housing the plate group and the electrolyte in the cell chamber.
[0165] Each plate in the plate group may be one or more. When the plate group includes two or more negative plates, if at least one negative plate satisfies the condition (condition a) that the negative electrode material contains the above-mentioned polymer compound, the effect of shifting the potential of the plate in a less noble direction is obtained according to the number of such negative plates, and the effect of reducing corrosion of the positive electrode collector during high-temperature float charging is obtained. From the viewpoint of further reducing corrosion of the positive electrode collector, it is preferable that 50% or more (more preferably 80% or more or 90% or more) of the number of negative plates included in the plate group are negative plates that satisfy condition a. The ratio of negative plates that satisfy condition a among the negative plates included in the plate group is 100% or less. All of the negative plates included in the plate group may satisfy condition a.
[0166] When the plate group includes two or more positive plates, from the viewpoint of ensuring higher life performance by reducing corrosion of the positive current collector during high-temperature float charging, it is preferable that 50% or more (more preferably 80% or more or 90% or more) of the number of positive plates included in the plate group are positive plates that satisfy the condition (condition b) that the Ca content in the positive current collector is 0.07 mass% or less. The ratio of the positive plates that satisfy condition b among the positive plates included in the plate group is 100% or less. All of the positive plates included in the plate group may satisfy condition b.
[0167] When a lead-acid battery has two or more cells, it is sufficient that the plate groups of at least some of the cells include negative plates that satisfy condition a and positive plates that satisfy condition b. From the viewpoint of ensuring higher high-temperature float life performance, it is preferable that 50% or more (more preferably 80% or more or 90% or more) of the number of cells included in the lead-acid battery include plate groups including negative plates that satisfy condition a and positive plates that satisfy condition b. The ratio of cells included in the lead-acid battery that include plate groups including negative plates that satisfy condition a and positive plates that satisfy condition b is 100% or less. It is preferable that all plate groups included in the lead-acid battery include negative plates that satisfy condition a and positive plates that satisfy condition b.
[0168] Fig. 1 is a perspective view showing an example of a lead-acid battery according to an embodiment of the present invention with the cover removed. Fig. 2A is a front view of the lead-acid battery shown in Fig. 1, and Fig. 2B is a schematic cross-sectional view of the section taken along line IIB-IIB in Fig. 2A as viewed from the direction of the arrow.
[0169] The lead-acid battery 1 includes a battery case 10 that contains an electrode plate group 11 and an electrolyte (not shown). The electrode plate group 11 is formed by stacking a plurality of negative electrode plates 2 and positive electrode plates 3 with separators 4 interposed therebetween. Here, a state in which a sheet-like separator 4 is sandwiched between the negative electrode plates 2 and the positive electrode plates 3 is shown, but the shape of the separator is not particularly limited.
[0170] An upwardly protruding current collecting lug (not shown) is provided at the top of each of the multiple negative electrode plates 2. An upwardly protruding current collecting lug (not shown) is also provided at the top of each of the multiple positive electrode plates 3. The lugs of the negative electrode plates 2 are connected and integrated with each other by a negative electrode strap 5a. Similarly, the lugs of the positive electrode plates 3 are connected and integrated with each other by a positive electrode strap 5b. The lower end of the negative electrode pole 6a is fixed to the upper part of the negative electrode strap 5a, and the lower end of the positive electrode pole 6b is fixed to the upper part of the positive electrode strap 5b.
[0171] (evaluation) The high temperature float life performance is evaluated based on the battery life when a capacity test is performed by HR discharge after float charging at high temperature. More specifically, the high temperature float life performance is evaluated by the following procedure.
[0172] The test battery is a valve-regulated lead-acid battery with a rated voltage of 2V and a rated capacity (10-hour rate) of 180Ah. In an environment of 60°C ±3°C, float charging is performed under constant voltage conditions of 2.23V / cell, and a capacity test is performed once a month at 25°C ±2°C. In the capacity test, the test battery is discharged until it reaches 1.0V / cell at a current (A) 3.0 times the value listed as the rated capacity (Ah), and the discharge time and discharge capacity at this time are obtained. After discharge, the battery is charged to 80% of the discharge capacity at a 5-hour rate (36A). Next, the battery is charged to 40% of the discharge capacity at a 20-hour rate (9A). The test period until the discharge time becomes less than 10 minutes is regarded as the life period, and is used as an index of high-temperature float life performance. The life period at 60°C obtained can be converted to the life years at 25°C by multiplying a specified index. The guideline is as follows. Life expectancy at 60°C is 12 months or more; at 25°C is 11-12 years Life expectancy at 60°C is 16 months or more; at 25°C is 15 years or more Life expectancy at 60°C is 22 months or more; expected life expectancy at 25°C is 20 years or more
[0173] A lead-acid battery according to one aspect of the present invention will be described below.
[0174] (1) A lead-acid battery, The lead-acid battery includes at least one cell including a plate group and an electrolyte; the electrode plate group includes a negative electrode plate, a positive electrode plate, and a separator interposed between the negative electrode plate and the positive electrode plate, The negative electrode plate includes a negative electrode current collector and a negative electrode material, The positive electrode plate includes a positive electrode current collector and a positive electrode material, The negative electrode material is measured using deuterated chloroform as a solvent. 1 The polymer compound has a peak in the range of 3.2 ppm to 3.8 ppm in the chemical shift of H-NMR spectrum, The Ca content in the positive electrode current collector is 0.07% by mass or less, The opposing area of the positive electrode plate and the negative electrode plate per 1 Ah of 10-hour capacity is 2450 mm2 / Ah or more 6700mm 2 / Ah or less.
[0175] (2) In the above (1), the polymer compound contains an oxygen atom bonded to an end group and a -CH- group and / or a -CH< group bonded to the oxygen atom, The above 1 In the H-NMR spectrum, the ratio of the integral of the peak to the sum of the integral of the peak, the integral of the peak due to the hydrogen atom of the -CH- group, and the integral of the peak due to the hydrogen atom of the -CH< group may be 85% or more.
[0176] (3) In the above (1) or (2), the polymer compound is oxyC 2-4 It may contain a repeating structure of alkylene units.
[0177] (4) A lead-acid battery, The lead-acid battery includes at least one cell including a plate group and an electrolyte; the electrode plate group includes a negative electrode plate, a positive electrode plate, and a separator interposed between the negative electrode plate and the positive electrode plate, The negative electrode plate includes a negative electrode current collector and a negative electrode material, The positive electrode plate includes a positive electrode current collector and a positive electrode material, The negative electrode material is oxyC 2-4 The polymer compound includes a repeating structure of an alkylene unit, The Ca content in the positive electrode current collector is 0.07% by mass or less, The opposing area of the positive electrode plate and the negative electrode plate per 1 Ah of 10-hour capacity is 2450 mm 2 / Ah or more 6700mm 2 / Ah or less.
[0178] (5) In any one of the above (1) to (4), the facing area is 3500 mm 2 / Ah or more or 4000mm 2 / Ah or more.
[0179] (6) In any one of the above (1) to (5), the facing area is 6500 mm 2 / Ah or less, 6100mm 2 / Ah or less, 5000mm 2 / Ah or less, or 4000mm 2 / Ah or less.
[0180] (7) In any one of the above (1) to (6), a ratio of the theoretical amount of electricity of the negative electrode plate to the theoretical amount of electricity of the positive electrode plate may be 0.6 or more, or 0.7 or more.
[0181] (8) In any one of the above (1) to (7), a ratio of the theoretical amount of electricity of the negative electrode plate to the theoretical amount of electricity of the positive electrode plate may be 1.3 or less.
[0182] (9) In any one of the above (1) to (8), the Sn content in the positive electrode current collector may be 7 mass% or less, 6 mass% or less, 5 mass% or less, 3 mass% or less, 2 mass% or less, 1.5 mass% or less, 1 mass% or less, 0.05 mass% or less, or less than 0.01 mass%.
[0183] (10) In any one of the above (1) to (9), the Sn content in the positive electrode current collector may be 0 mass% or more, 0.01 mass% or more, 0.3 mass% or more, 0.5 mass% or more, 0.8 mass% or more, or 1 mass% or more.
[0184] (11) In any one of the above (1) to (10), the Ca content in the positive electrode current collector may be 0.07% by mass or less, 0.06% by mass or less, or less than 0.01% by mass.
[0185] (12) In any one of the above (1) to (11), the Ca content in the positive electrode current collector may be 0 mass % or more, or 0.01 mass % or more.
[0186] (13) In any one of the above (1) to (8), when the Ca content in the positive electrode current collector is 0.01 mass% or more (e.g., 0.01 mass% or more and 0.06 mass% or less), the Sn content in the positive electrode current collector may be 0.01 mass% or more (e.g., 0.8 mass% or more (or 1 mass% or more) and 3 mass% or less).
[0187] (14) In any one of the above (1) to (8), when the Ca content in the positive electrode current collector is less than 0.01 mass%, the Sn content in the positive electrode current collector may be 2 mass% or less, 1.5 mass% or less, 1 mass% or less, 0.05 mass% or less, or less than 0.01 mass%.
[0188] (15) In the above (14), the Sn content in the positive electrode current collector may be 0 mass % or more.
[0189] (16) In any one of the above (1) to (15), the lead-acid battery may be a valve regulated battery.
[0190] (17) In any one of the above (1) to (16), the polymer compound may include a compound having an Mn of 5 million or less, 1 million or less, 100,000 or less, 20,000 or less, 10,000 or less, 5,000 or less, 4,000 or less, 3,700 or less, or 3,500 or less.
[0191] (18) In any one of the above (1) to (17), the polymer compound may include a compound having an Mn of 300 or more, 400 or more, 500 or more, 800 or more, or 1,000 or more.
[0192] (19) In any one of the above (1) to (18), the polymer compound is an oxyC 2-4 The compound includes at least one selected from the group consisting of a hydroxy compound having a repeating alkylene unit structure, an etherified product of the hydroxy compound, and an esterified product of the hydroxy compound, The hydroxy compound is polyC 2-4 Alkylene glycol, oxy C2-4 Copolymers containing repeating alkylene units, and polyol polyC 2-4 It may be at least one selected from the group consisting of alkylene oxide adducts.
[0193] (20) In any one of the above (1) to (19), the polymer compound may contain a repeating structure of an oxypropylene unit.
[0194] (21) In the above (20), the polymer compound is polypropylene glycol, polyoxypropylene-polyoxyethylene copolymer (polyoxypropylene-polyoxyethylene block copolymer, etc.), polypropylene glycol alkyl ether (the above R 2 alkyl ethers (methyl ether, ethyl ether, butyl ether, etc.) in which R is an alkyl having 10 or less carbon atoms (or 8 or less or 6 or less), polyoxyethylene-polyoxypropylene alkyl ethers (the above R 2 alkyl ethers (butyl ether, hydroxyhexyl ether, etc.) in which R is an alkyl having 10 or less carbon atoms (or 8 or less or 6 or less), polypropylene glycol carboxylates (the above R 3 may contain at least one selected from the group consisting of polypropylene glycol carboxylates (such as polypropylene glycol acetate) in which the alkyl group has 10 or less carbon atoms (or 8 or less, or 6 or less), and polypropylene oxide adducts of triol or higher polyols (such as polypropylene oxide adducts of glycerin).
[0195] (22) In any one of the above (1) to (19), the polymer compound may have one or more hydrophobic groups, and at least one of the hydrophobic groups may be a long-chain aliphatic hydrocarbon group having 8 or more carbon atoms.
[0196] (23) In the above (22), the long-chain aliphatic hydrocarbon group may have 12 or more carbon atoms or 16 or more carbon atoms.
[0197] (24) In the above (22) or (23), the long-chain aliphatic hydrocarbon group may have 30 or less, 26 or less, or 22 or less carbon atoms.
[0198] (25) In any one of the above (19) and (22) to (24), the polymer compound may contain a repeating structure of an oxyethylene unit.
[0199] (26) In the above (25), the polymer compound may comprise at least one selected from the group consisting of etherified polyethylene glycol (e.g., alkyl ethers), esterified polyethylene glycol (e.g., carboxylates), etherified polyethylene oxide adducts of the above polyols (e.g., alkyl ethers), and esterified polyethylene oxide adducts of polyols (e.g., triols or higher polyols).
[0200] (27) In the above (25) or (26), the polymer compound may include at least one selected from the group consisting of polyethylene glycol oleate, polyethylene glycol dioleate, polyethylene glycol dilaurate, polyethylene glycol distearate, polyoxyethylene coconut oil fatty acid sorbitan, polyoxyethylene sorbitan oleate, polyoxyethylene sorbitan stearate, polyoxyethylene lauryl ether, polyoxyethylene tetradecyl ether, and polyoxyethylene cetyl ether.
[0201] (28) In any one of the above (22) to (27), the polymer compound may have an HLB of 4 or more, or 4.3 or more.
[0202] (29) In any one of the above (22) to (28), the polymer compound may have an HLB of 18 or less, 10 or less, 9 or less, or 8.5 or less.
[0203] (30) In any one of the above (1) to (29), the content of the polymer compound in the negative electrode material may be 3 ppm or more, 5 ppm or more, 80 ppm or more, or 100 ppm or more.
[0204] (31) In any one of the above (1) to (30), the content of the polymer compound in the negative electrode material may be 5000 ppm or less, 3000 ppm or less, 2000 ppm or less, 1000 ppm or less, less than 1000 ppm, 700 ppm or less, or 500 ppm or less.
[0205] (32) In any one of the above (1) to (31), the negative electrode material may contain an organic shrinkage preventer.
[0206] (33) In the above (32), the content of the organic shrink-preventing agent in the negative electrode material may be 0.005% by mass or more, or 0.01% by mass or more.
[0207] (34) In the above (32) or (33), the content of the organic shrink-preventing agent in the negative electrode material may be 1.0 mass % or less, 0.5 mass % or less, or 0.2 mass % or less.
[0208] (35) In any one of the above (1) to (34), the negative electrode material may contain a carbonaceous material.
[0209] (36) In the above (35), the content of the carbonaceous material in the negative electrode material may be 0.05% by mass or more, or 0.10% by mass or more.
[0210] (37) In the above (35) or (36), the content of the carbonaceous material in the negative electrode material may be 5% by mass or less, or 3% by mass or less.
[0211] (38) In any one of the above (1) to (37), the negative electrode material may further contain barium sulfate.
[0212] (39) In the above (38), the content of the barium sulfate in the negative electrode material may be 0.05% by mass or more, or 0.10% by mass or more.
[0213] (40) In the above (38) or (39), the content of the barium sulfate in the negative electrode material may be 3 mass % or less, or 2 mass % or less.
[0214] (41) In any one of the above (1) to (40), the specific gravity of the electrolyte in a fully charged lead-acid battery at 20° C. may be 1.20 or more, or 1.25 or more.
[0215] (42) In any one of the above (1) to (41), the specific gravity of the electrolyte in a fully charged lead-acid battery at 20° C. may be 1.35 or less or 1.32 or less.
[0216] [Example] The present invention will be specifically described below based on examples and comparative examples, but the present invention is not limited to the following examples.
[0217] Lead-acid batteries E1 to E40 and C1 to C19 (1) Preparation of lead-acid battery (a) Preparation of the negative electrode plate The raw lead powder, the polymer compound shown in the table, sodium lignin sulfonate, carbonaceous material (carbon black), and barium sulfate are mixed with an appropriate amount of sulfuric acid aqueous solution to obtain a negative electrode paste. At this time, the components are mixed so that the content of the polymer compound in the negative electrode material, which is obtained by the procedure described above, is the value shown in the table, and the content of sodium lignin sulfonate is 0.1 mass%, the content of carbon black is 0.2 mass%, and the content of barium sulfate is 0.4 mass%. The negative electrode paste is filled into the mesh part of a casting grid made of a Pb-Ca-Sn alloy, and aged and dried to obtain an unformed negative electrode plate.
[0218] In addition, when the polymer compound has a repeating structure of oxyethylene units, the molecular weight of the polymer compound measured by the above-mentioned procedure 1 In the H-NMR spectrum, a peak derived from -CH2- of the oxyethylene unit is observed in the chemical shift range of 3.2 ppm to 3.8 ppm. When the polymer compound has a repeating structure of oxypropylene units, the NMR spectrum of the polymer compound measured by the above-mentioned procedure 1 In the H-NMR spectrum, peaks derived from -CH2- of the oxypropylene unit are observed in the chemical shift range of 3.2 ppm to 3.42 ppm, and peaks derived from -CH< and -CH2- of the oxypropylene unit are observed in the chemical shift range of more than 3.42 ppm to 3.8 ppm. 1 In the H-NMR spectrum, the percentage of the integral of the peak between 3.2 ppm and 3.8 ppm to the total integral of this peak, the integral of the peak of the hydrogen atom of the -CH2- group bonded to the oxygen atom, and the integral of the peak of the hydrogen atom of the -CH< group bonded to the oxygen atom is 96 to 100%.
[0219] (b) Preparation of the positive electrode plate The raw lead powder is mixed with an aqueous sulfuric acid solution to obtain a positive electrode paste. The positive electrode paste is filled into the mesh of a cast grid made of Pb or Pb alloy as a positive electrode collector, and aged and dried to obtain an unformed positive electrode plate. As the Pb alloy, a Pb-Sn alloy or a Pb-Ca-Sn alloy is used. The Ca content and Sn content of the positive electrode collector obtained by the above-mentioned procedure are the values shown in the table. In the test battery of Table 5, the amount of the negative electrode material and the positive electrode material filled into the collector is adjusted so that the theoretical electrical quantity ratio is the value shown in the table.
[0220] (c) Preparation of test battery A valve-regulated lead-acid battery with a rated voltage of 2V and a rated capacity (10-hour rate) of 180Ah is prepared. Positive and negative plates are stacked with a glass fiber nonwoven separator between them to form a plate group. The number and thickness of the positive and negative plates included in the plate group of the test battery are adjusted so that the opposing area of each plate obtained by the above-mentioned procedure is the value shown in the table. The plate group is placed in a polypropylene container together with an electrolyte (aqueous sulfuric acid solution), and chemical formation is performed in the container to prepare a valve-regulated lead-acid battery. The specific gravity of the electrolyte in a fully charged lead-acid battery at 20°C is 1.28.
[0221] (2) Evaluation Using the above test battery, a capacity test is carried out by HR discharge according to the procedure described above, and the initial discharge time (min) is measured. In addition, the test battery is used to evaluate the high temperature float life performance (life period (months)) by a capacity test using HR discharge according to the procedure described above. The evaluation results are shown in Tables 1 to 5. In the tables, E1 to E40 are working examples, and C1 to C19 are comparative examples. Table 4 also shows the Mn of the polymer compounds. The Mn of polypropylene glycol is the Mn determined by the above-mentioned procedure. The Mn of the esterified product or etherified product is the Mn of the etherified product or esterified product used in the preparation of the negative electrode material.
[0222] [Table 1]
[0223] As shown in Table 1, the opposing area of each electrode plate is 2450 mm 2 At less than 2450mm / Ah, no difference was observed in the high-temperature float life performance in the capacity test at HR discharge between negative electrode materials that contained polymer compounds and those that did not (comparison of C1 and C2 with C7 and C8). 2 / Ah or more, the negative electrode material containing a polymer compound significantly improves the high temperature float life performance in the capacity test with HR discharge compared to when the polymer compound is not included (comparison of C3 to C6 and E1 to E4). 2 / Ah range, the initial discharge time is long and high HR discharge performance is obtained.
[0224] When checking the cause of the lifespan of test batteries that had reached the end of their lifespan in the evaluation of high-temperature float life performance, it was found that when the negative electrode material did not contain a polymer compound, the opposing area of the positive electrode plate and the negative electrode plate was 2050 mm 2 / Ah or less is a negative electrode regulation that ends the life of the negative electrode due to deterioration of the electrode material, 2450mm 2 / Ah or more, the positive electrode collector will corrode and the battery will reach its end of life. In other words, if the negative electrode material does not contain a polymer compound, the facing area of the positive plate and the negative plate will be 2450 mm 2 / Ah or more, corrosion of the positive electrode current collector has a large effect on the lifespan. Therefore, the high temperature float life performance is likely to decrease when discharging at HR.
[0225] When the negative electrode material contains a polymer compound, the facing area of the positive electrode plate and the negative electrode plate is 4000 mm 2 / Ah or less is the negative electrode regulation, where the deterioration of the negative electrode material is the end of the lifespan, and 2 / Ah or more, the corrosion of the positive electrode current collector is the limiting factor for the life of the battery. In other words, the polymer compound reduces the corrosion rate of the positive electrode current collector over a wide area of the opposing surface, and high-temperature float life performance can be obtained even when discharging at high temperature.
[0226] In addition, when each of the lead-acid batteries C8 and E1 is float-charged according to the above-mentioned procedure and a capacity test is performed every month at 25°C ± 2°C under mild discharge conditions (low-rate discharge conditions), excellent life performance is obtained in both cases. More specifically, the discharge in the capacity test is performed until 1.8V / cell is reached at a current (A) that is 0.1 times the value described as the rated capacity (Ah). The test period until the discharge time becomes less than 8 hours is the life period. In this case, the life period of the lead-acid battery C8 is 16 months, and the life period of the lead-acid battery E1 is 15 months. In other words, the behavior of the life period when the facing area of the positive electrode plate and the negative electrode plate is changed is completely different depending on whether the discharge rate after the high-temperature float charge is high or low. In the case of low-rate discharge conditions, the problem of the life period after the high-temperature float test being reduced depending on the facing area of the positive electrode plate and the negative electrode plate does not occur.
[0227] [Table 2]
[0228] As shown in Table 2, when the Ca content in the positive electrode collector exceeds 0.07% by mass, even when the negative electrode material contains a polymer compound, the effect of improving the high-temperature float life performance when discharged at HR is very small (compare C12 and C13). In contrast, when the Ca content in the positive electrode collector is 0.07% by mass or less, the high-temperature float life performance when discharged at HR is significantly improved by the inclusion of a polymer compound in the negative electrode material (compare C9 to C11 and C5 with E5 to E7 and E3).
[0229] [Table 3]
[0230] As shown in Table 3, when the positive electrode current collector contains Ca (preferably when the Ca content is 0.01 mass% or more), a relatively high Sn content tends to provide higher high-temperature float life performance (comparison of E9 with E3, E6 to E7, and E10 to E17). From the viewpoint of ensuring higher high-temperature float life performance, the Sn content is preferably 0.5 mass% or more, and more preferably 1 mass% or more. In addition, when the Sn content is high, a β phase, which is a Sn-rich phase, tends to be formed, and the corrosion rate tends to increase. Therefore, from the viewpoint of further reducing the corrosion of the positive electrode current collector and ensuring higher high-temperature float life performance, the Sn content is more preferably 3 mass% or less. Note that, in E8 and E9, grain boundary corrosion tends to progress easily, and it is considered that the high-temperature float life performance was slightly reduced.
[0231] When checking the cause of the lifespan of the test batteries that reached the end of their life in the evaluation of high-temperature float life performance, it was found that the cause was the deterioration of the negative electrode material in E5, E6, E11, E13, and E7 (negative electrode regulation). Therefore, it is believed that in these batteries, the corrosion of the positive electrode current collector is reduced, resulting in higher high-temperature float life performance.
[0232] [Table 4]
[0233] As shown in Table 4, oxyC 2-4 Even when a hydroxy compound having a repeating alkylene unit structure or an etherified product of a hydroxy compound is used, a high high-temperature float life performance can be ensured when discharging at HR.
[0234] From the viewpoint of easily obtaining higher high-temperature float life performance, the content of the polymer compound in the negative electrode material is preferably 3 ppm or more, and more preferably 5 ppm or more, by mass. From the same viewpoint, the content of the polymer compound is preferably 3000 ppm or less, more preferably 2000 ppm or less, and may be 1000 ppm or less or 500 ppm or less, by mass.
[0235] From the viewpoint of ensuring higher high-temperature float life performance, the HLB of the polymer compound is preferably 4 or more (or 4.3 or more) and 9 or less, or 4 or more (or 4.3 or more) and 8.5 or less.
[0236] [Table 5]
[0237] As shown in Table 5, from the viewpoint of easily ensuring higher high-temperature float life performance, the theoretical electrical quantity ratio of the negative electrode plate to the positive electrode plate is preferably 0.7 or more and 1.3 or less. [Industrial Applicability]
[0238] Each of the lead-acid batteries according to the first and second aspects of the present invention can be applied to, for example, a valve-regulated lead-acid battery. Specifically, the lead-acid battery can be used as a stationary industrial power storage device (such as for UPS), a starting power source for a vehicle, or a power source for auxiliary equipment. Note that these uses are merely examples, and the use is not limited to these uses. [Explanation of symbols]
[0239] 1:Lead acid battery 2: Negative plate 3: Positive plate 4: Separator 5a: Negative electrode strap 5b: Positive electrode strap 6a: Negative pole 6b: Positive pole 10: Battery case 11: Plate group
Claims
1. A lead-acid battery, The lead-acid battery includes at least one cell including a plate group and an electrolyte; the electrode plate group includes a negative electrode plate, a positive electrode plate, and a separator interposed between the negative electrode plate and the positive electrode plate, The negative electrode plate includes a negative electrode current collector and a negative electrode material, The positive electrode plate includes a positive electrode current collector and a positive electrode material, The negative electrode material is measured using deuterated chloroform as a solvent. 1 The polymer compound has a peak in the range of 3.2 ppm to 3.8 ppm in terms of the chemical shift in the H-NMR spectrum, The Ca content in the positive electrode current collector is 0.07% by mass or less, The opposing area of the positive electrode plate and the negative electrode plate per 1 Ah of 10-hour capacity is 2450 mm 2 / Ah or more 6700mm 2 / Ah or less, the polymer compound comprises at least one selected from the group consisting of a hydroxy compound having a repeating structure of an oxyC 2-4 alkylene unit, an etherified product of the hydroxy compound, and an esterified product of the hydroxy compound, A lead-acid battery, wherein the hydroxy compound is at least one selected from the group consisting of polyC 2-4 alkylene glycol, a copolymer containing a repeating structure of oxyC 2-4 alkylene, and a polyC 2-4 alkylene oxide adduct of a polyol.
2. A lead-acid battery, The lead-acid battery includes at least one cell including a plate group and an electrolyte; the electrode plate group includes a negative electrode plate, a positive electrode plate, and a separator interposed between the negative electrode plate and the positive electrode plate, The negative electrode plate includes a negative electrode current collector and a negative electrode material, The positive electrode plate includes a positive electrode current collector and a positive electrode material, The negative electrode material is measured using deuterated chloroform as a solvent. 1 The polymer compound has a peak in the range of 3.2 ppm to 3.8 ppm in terms of the chemical shift in the H-NMR spectrum, The Ca content in the positive electrode current collector is 0.07% by mass or less, The opposing area of the positive electrode plate and the negative electrode plate per 1 Ah of 10-hour capacity is 2450 mm 2 / Ah or more 6700mm 2 / Ah or less, The polymer compound comprises a repeating structure of oxypropylene units.
3. A lead-acid battery, The lead-acid battery includes at least one cell including a plate group and an electrolyte; The electrode plate group includes a negative electrode plate, a positive electrode plate, and a separator interposed between the negative electrode plate and the positive electrode plate. and a radar. The negative electrode plate includes a negative electrode current collector and a negative electrode material, The positive electrode plate includes a positive electrode current collector and a positive electrode material, The negative electrode material is measured using deuterated chloroform as a solvent. 1 H-NMR Spec In the chemical shift of the spectrum, a peak is observed in the range of 3.2 ppm to 3.8 ppm. The polymer compound includes a The Ca content in the positive electrode current collector is 0.07% by mass or less, The opposing area of the positive electrode plate and the negative electrode plate per 1 Ah of 10-hour capacity is 2450 mm 2 / Ah or more 6700mm 2 / Ah or less, the polymer compound comprises at least one selected from the group consisting of a hydroxy compound having a repeating structure of an oxyC 2-4 alkylene unit, an etherified product of the hydroxy compound, and an esterified product of the hydroxy compound, the hydroxy compound is at least one selected from the group consisting of polyC 2-4 alkylene glycol, a copolymer containing a repeating unit of oxyC 2-4 alkylene, and a polyC 2-4 alkylene oxide adduct of a polyol; The polymer compound has one or more hydrophobic groups, At least one of the hydrophobic groups is a long-chain aliphatic hydrocarbon group having 8 or more carbon atoms.
4. A lead-acid battery, The lead-acid battery includes at least one cell including a plate group and an electrolyte; the electrode plate group includes a negative electrode plate, a positive electrode plate, and a separator interposed between the negative electrode plate and the positive electrode plate, The negative electrode plate includes a negative electrode current collector and a negative electrode material, The positive electrode plate includes a positive electrode current collector and a positive electrode material, The negative electrode material is measured using deuterated chloroform as a solvent. 1 The polymer compound has a peak in the range of 3.2 ppm to 3.8 ppm in terms of the chemical shift in the H-NMR spectrum, The Ca content in the positive electrode current collector is 0.07% by mass or less, The opposing area of the positive electrode plate and the negative electrode plate per 1 Ah of 10-hour capacity is 2450 mm 2 / Ah or more 6700mm 2 / Ah or less, The polymer compound contains a repeating structure of oxyethylene units.
5. The polymer compound has an oxygen atom bonded to a terminal group and a —CH 2 - and / or -CH< groups, The above 1 In the H-NMR spectrum, the integral value of the peak and the integral value of the -CH 2 The lead acid battery according to any one of claims 1 to 4, wherein the ratio of the integral value of the peak of the hydrogen atom of the - group to the integral value of the peak of the hydrogen atom of the -CH< group in the total is 85% or more.
6. A lead-acid battery, The lead-acid battery includes at least one cell including a plate group and an electrolyte; the electrode plate group includes a negative electrode plate, a positive electrode plate, and a separator interposed between the negative electrode plate and the positive electrode plate, The negative electrode plate includes a negative electrode current collector and a negative electrode material, The positive electrode plate includes a positive electrode current collector and a positive electrode material, The negative electrode material is oxyC 2-4 The polymer compound includes a repeating structure of an alkylene unit, The Ca content in the positive electrode current collector is 0.07% by mass or less, The opposing area of the positive electrode plate and the negative electrode plate per 1 Ah of 10-hour capacity is 2450 mm 2 / Ah or more 6700mm 2 / Ah or less.
7. The polymer compound is 2-4 The compound includes at least one selected from the group consisting of a hydroxy compound having a repeating alkylene unit structure, an etherified product of the hydroxy compound, and an esterified product of the hydroxy compound, The hydroxy compound is polyC 2-4 Alkylene glycol, oxy C 2-4 A copolymer containing a repeating alkylene unit and a polyol, polyC 2-4 The lead-acid battery according to claim 6 , wherein the compound is at least one selected from the group consisting of alkylene oxide adducts.
8. The lead acid battery according to claim 7 , wherein the polymer compound comprises a repeating structure of oxypropylene units.
9. The polymer compound has one or more hydrophobic groups, 8. The lead-acid battery according to claim 7, wherein at least one of the hydrophobic groups is a long-chain aliphatic hydrocarbon group having 8 or more carbon atoms.
10. The lead acid battery according to claim 7 or 9, wherein the polymer compound contains a repeating structure of oxyethylene units.
11. The lead acid battery according to any one of claims 1 to 10, wherein the Sn content in the positive electrode current collector is 7 mass% or less.
12. The Ca content in the positive electrode current collector is less than 0.01 mass %, The lead acid battery according to any one of claims 1 to 11, wherein the Sn content in the positive electrode current collector is 2 mass% or less.
13. The lead acid battery according to any one of claims 1 to 12, wherein the content of the polymer compound in the negative electrode material is 3 ppm or more.
14. The ratio of the theoretical amount of electricity of the negative electrode plate to the theoretical amount of electricity of the positive electrode plate is 0.7 or more and 1.3 or less. The lead acid battery according to any one of claims 1 to 13, wherein:
15. The lead acid battery according to any one of claims 1 to 14, which is a valve regulated battery.
Citation Information
Patent Citations
Namarichikudenchoinkyokuban
JP1976047237A
Lead-acid battery
JP1985182662A
Macromolecular solid electrolyte, its material and use
JP1996311138A
Negative electrode plate for lead-acid battery and lead-acid battery
JP1997147874A
Sealed lead-acid battery
JP1999191409A